Carbon negative electrode material and preparation method thereof, lithium ion battery negative electrode, lithium ion battery and electrical equipment

By distributing sodium and/or potassium elements between the carbon layers of the carbon anode material and adopting specific preparation methods, the problem of improving the performance of carbon anode material in the prior art is solved, and a comprehensive performance of high capacity, high magnification and low expansion is achieved.

CN115377414BActive Publication Date: 2025-03-21BTR NEW MATERIAL GRP CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110536116.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-05-17
Publication Date
2025-03-21
Estimated Expiration
2041-05-17

AI Technical Summary

Technical Problem

While improving capacity performance, existing carbon negative electrode materials are prone to decrease in use voltage, attenuation of power and cyclic performance, increase in internal resistance, and increase in expansion rate, making it difficult to have high capacity, high magnification and low expansion performance.

Method used

By distributing sodium and/or potassium elements between carbon layers of the carbon matrix, controlling the carbon layer spacing, and using specific preparation methods, including pretreatment, intercalation reaction and post-treatment, the capacity and rate performance of the carbon anode material are improved while reducing the expansion rate.

Benefits of technology

It has achieved the improvement of the capacity and rate performance of carbon anode materials, while reducing the expansion rate and improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115377414B_ABST
    Figure CN115377414B_ABST
Patent Text Reader

Abstract

The present application provides a carbon negative electrode material and a preparation method thereof, a lithium ion battery negative electrode, a lithium ion battery and an electrical device. The carbon negative electrode material comprises a carbon matrix and an alkali metal element, the alkali metal element is distributed between the carbon layers of the carbon negative electrode material, the alkali metal element comprises sodium element and / or potassium element, and the carbon layer spacing of the carbon negative electrode material is 0.35nm-0.43nm. The preparation method of the carbon negative electrode material comprises: subjecting the carbon source to pre-treatment, intercalation reaction and post-treatment in sequence to obtain the carbon negative electrode material. The negative electrode of a lithium ion battery comprises the carbon negative electrode material. The lithium ion battery comprises the lithium ion battery negative electrode. The electrical device comprises the lithium ion battery. The carbon negative electrode material provided in the present application has high capacity and low expansion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of lithium-ion batteries, and in particular to a carbon negative electrode material and a preparation method thereof, a lithium-ion battery negative electrode, a lithium-ion battery and electrical equipment. Background Art

[0002] Generally speaking, the main way to increase the energy density of carbon negative electrode materials is to increase the specific capacity of carbon. The main methods include: doping modification, modification by alkali activation, screening of specific carbon sources, oxidation modification, etc.

[0003] However, although the capacity of carbon negative electrode materials can be improved by heteroatom doping, it often leads to a decrease in their operating voltage, a decrease in power and cycle performance, and an increase in internal resistance; improving the capacity performance of carbon negative electrode materials by alkali activation will lead to an increase in the specific surface area of ​​the carbon negative electrode materials, an increase in the irreversible capacity generated by the SEI film, a decrease in the first efficiency, and an increase in the cost of use; in addition, the micropores generated by activation can easily cause the carbon negative electrode materials to produce dead lithium during the cycle, resulting in a decrease in cycle performance; the oxidation method improves the capacity of carbon negative electrode materials, but the preparation conditions are relatively demanding and it is not suitable for large-scale production. In addition, the above methods often lead to an increase in the expansion rate of carbon negative electrode materials.

[0004] Currently, the development of new carbon negative electrode materials with high capacity, high rate and low expansion faces technical bottlenecks. Summary of the invention

[0005] The purpose of the present application is to provide a carbon negative electrode material and a preparation method thereof, a lithium ion battery negative electrode, a lithium ion battery and an electrical device to solve the above problems.

[0006] In order to achieve the above objectives, this application adopts the following technical solutions:

[0007] A carbon negative electrode material, comprising a carbon matrix and an alkali metal element, wherein the alkali metal element is distributed between carbon layers of the carbon negative electrode material, wherein the alkali metal element comprises sodium and / or potassium, and wherein the carbon layer spacing of the carbon negative electrode material is 0.35nm-0.43nm.

[0008] In an optional embodiment, the carbon matrix is ​​doped with heteroelements;

[0009] In an optional embodiment, the heteroelement includes S and / or P;

[0010] In an optional embodiment, the proportion of the impurity elements to the total mass of the carbon negative electrode material is no more than 4%;

[0011] In an optional embodiment, the mass of the alkali metal element accounts for no more than 3% of the total mass of the carbon negative electrode material;

[0012] and / or, the alkali metal element exists between the carbon layers in the form of ACx, wherein A is Na and / or K, and x>8;

[0013] In an optional embodiment, the specific surface area of ​​the carbon negative electrode material is 0.5 m 2 / g-10m 2 / g;

[0014] In an optional embodiment, the true density of the carbon negative electrode material is 1.8 g / cc-2.6 g / cc;

[0015] In an optional embodiment, the median particle size of the carbon negative electrode material is 2 μm-40 μm.

[0016] The present application also provides a method for preparing a carbon negative electrode material, comprising:

[0017] The carbon source is subjected to pre-treatment, intercalation reaction and post-treatment in sequence to obtain the carbon negative electrode material.

[0018] In an optional embodiment, the pre-processing includes:

[0019] Performing a first pre-carbonization and a first sintering on the raw materials including the carbon source to obtain a first precursor;

[0020] Mixing and coating materials including the first precursor and a sacrificial carbon source, and then curing and oxidizing to obtain a second precursor;

[0021] In an optional embodiment, the carbon source includes a hard carbon source, and the hard carbon source includes at least one of phenolic resin, epoxy resin, melamine resin, furfural resin, acrylic resin, starch, glucose, sucrose, fructose, asphalt, almond shell, coconut shell, peach shell, walnut shell, jujube shell, polyfurfuryl alcohol, polyphenylene, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile;

[0022] In an optional embodiment, the first pre-carbonization temperature is 400°C-600°C, and the time is 0.5h-4h;

[0023] In an optional embodiment, a first pulverization process is further included after the first pre-carbonization and before the first sintering;

[0024] In an optional embodiment, the median particle size of the pulverized material obtained by the first pulverization process is 2 μm-40 μm;

[0025] In an optional embodiment, the median particle size of the pulverized material obtained by the first pulverization process is 5 μm-20 μm;

[0026] In an optional embodiment, the median particle size of the pulverized material obtained by the first pulverization process is 6 μm-15 μm;

[0027] In an optional embodiment, a first purification process is further included after the first pulverization process and before the first sintering;

[0028] In an optional embodiment, the first purification treatment comprises: mixing the material including the crushed material, the first acid and water, performing a first washing with water after immersion, and then performing a first drying;

[0029] In an optional embodiment, the first acid includes at least one of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, perchloric acid, acetic acid and benzoic acid;

[0030] In an optional embodiment, the mass ratio of the pulverized material, the first acid and water is 1:(0.2-2):(5-10);

[0031] In an optional embodiment, the immersion time is 12h-48h;

[0032] In an alternative embodiment, the material is washed with water to a pH of 6-7;

[0033] In an optional embodiment, the water is pure water or deionized water;

[0034] In an optional embodiment, the first drying temperature is 80°C-120°C, and the time is 24h-48h;

[0035] In an optional embodiment, after the first purification and before the first sintering, the method further includes: performing a first doping on the purified material using a first impurity element source;

[0036] In an optional embodiment, the first heteroelement source includes a phosphorus source and / or a sulfur source;

[0037] In an optional embodiment, the phosphorus source includes at least one of phosphorus pentoxide, phosphorus trioxide, ammonium phosphate, ammonium dihydrogen phosphate, diamine hydrogen phosphate and phosphoric acid;

[0038] In an alternative embodiment, the sulfur source includes at least one of sulfur powder, sodium thiosulfate, ammonium sulfide, ammonium bisulfide, ammonium bisulfide and thioanisole;

[0039] In an optional embodiment, the mass ratio of the purified material to the first impurity element source is (99-70):(1-30);

[0040] In an optional embodiment, the first sintering is performed under a first protective atmosphere;

[0041] In an optional embodiment, the first protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton;

[0042] In an optional embodiment, the first sintering temperature is 1000° C.-1300° C., and the time is 0.5 h-12 h;

[0043] In an alternative embodiment, the sacrificial carbon source includes at least one of asphalt, glucose, sucrose, fructose, epoxy resin, phenolic resin, furfural resin, urea-formaldehyde resin, acrylic resin, polystyrene, polyvinyl alcohol, polyvinyl chloride, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile;

[0044] In an optional embodiment, the mass ratio of the sacrificial carbon source to the first precursor is (1-10): (99-90);

[0045] In an optional embodiment, the mixed coating method includes solid phase mixed coating, liquid phase mixed coating and heating melt coating;

[0046] In an optional embodiment, the curing comprises: heating and curing the mixed and coated material under a second protective atmosphere;

[0047] In an optional embodiment, the second protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton;

[0048] In an optional embodiment, the temperature of the heating and curing is 100°C-300°C;

[0049] In an optional embodiment, the oxidation includes: subjecting the solidified material to a first heating treatment in an oxygen-containing atmosphere;

[0050] In an optional embodiment, the mass percentage of oxygen in the oxygen-containing atmosphere is 5%-100%;

[0051] In an optional embodiment, the oxygen-containing atmosphere is air;

[0052] In an optional embodiment, the temperature of the first heat treatment is 200°C-350°C, the heating rate is 0.5°C / min-5°C / min, and the holding time is 0.5h-3h.

[0053] In an alternative embodiment, the intercalation reaction comprises:

[0054] Mixing materials including the second precursor and an active additive for providing sodium or potassium, heating for reaction, and then cooling to obtain the carbon negative electrode material;

[0055] In an optional embodiment, the active additive includes at least one of sodium hydroxide, sodium oxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium hyponitrite, sodium hypochlorite, sodium oxalate, sodium acetate, sodium amide, sodium ethoxide, potassium hydroxide, potassium oxide, potassium carbonate, potassium bicarbonate, potassium nitrate, potassium hyponitrite, potassium hypochlorite, potassium oxalate, potassium acetate, potassium amide and potassium ethoxide;

[0056] In an optional embodiment, the mass ratio of the second precursor to the active additive is 1:(0.5-2);

[0057] In an optional embodiment, the particle size of the active additive is less than or equal to 30 mesh;

[0058] In an optional embodiment, the mixing of the second precursor and the active additive is carried out by a VC machine, the rotation speed of the VC machine is 500r / min-3000r / min, and the mixing time is 5min-40min;

[0059] In an optional embodiment, the temperature of the heating reaction is 650°C-850°C, the heating rate is 0.5°C / min-5°C / min, and the holding time is 20min-60min;

[0060] In an optional embodiment, the heating reaction is carried out in a third protective atmosphere, and the third protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton;

[0061] In an optional embodiment, the cooling end point temperature is less than or equal to 120°C.

[0062] In an optional embodiment, the post-processing includes:

[0063] The cooled material is mixed with water, washed until the pH is less than or equal to 10, then a neutralizing substance is added, filtered and washed until the pH is 6-7, and then a second drying is performed;

[0064] In an optional embodiment, the neutralizing substance includes at least one of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, perchloric acid, acetic acid and benzoic acid;

[0065] In an optional embodiment, the second drying is performed at a temperature of 80° C. to 120° C. for a time of 24 h to 36 h.

[0066] In an optional embodiment, the pre-processing includes:

[0067] performing a second pre-carbonization on the raw materials including the carbon source to obtain a third precursor;

[0068] Mixing materials including the third precursor and an oxidizing solution to perform oxidation expansion modification to obtain a fourth precursor;

[0069] In an optional embodiment, the carbon source includes a difficult-graphitizable carbon source and / or an easily-graphitizable carbon source;

[0070] In an optional embodiment, the non-graphitizable carbon source includes at least one of a natural biomass carbon source, a plant extract carbon source, and a polymer carbon source;

[0071] In an optional embodiment, the natural biomass carbon source includes at least one of coconut shell, almond shell, pistachio shell, macadamia shell, date shell, peanut shell, walnut shell, peach shell, cotton, gelatin, sawdust, bamboo, straw, kelp and lignin;

[0072] In an alternative embodiment, the plant extract carbon source includes at least one of starch, glucose, sucrose, fructose and natural rubber;

[0073] In an optional embodiment, the polymer carbon source includes at least one of phenolic resin, epoxy resin, melamine resin, polyfurfuryl alcohol, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin and polyacrylonitrile;

[0074] In an optional embodiment, the graphitizable carbon source includes at least one of asphalt, petroleum coke, mesocarbon microbeads and polyphenylene;

[0075] In an optional embodiment, the temperature of the second pre-carbonization is 400°C-700°C, and the time is 0.5h-10h;

[0076] In an optional embodiment, the second pre-carbonization is performed under a fourth protective atmosphere, and the fourth protective atmosphere includes at least one of nitrogen, argon, neon, helium, xenon and krypton;

[0077] In an optional embodiment, after the second pre-carbonization, the method further comprises: performing a second doping on the second pre-carbonized material using a second impurity element source;

[0078] In an optional embodiment, the second doping includes: mixing the second pre-carbonized material with a second impurity element source, and performing a second sintering in an inert gas atmosphere;

[0079] In an optional embodiment, the second heteroelement source includes a phosphorus source and / or a sulfur source;

[0080] In an optional embodiment, the phosphorus source includes at least one of phosphorus pentoxide, phosphorus trioxide, ammonium phosphate, ammonium dihydrogen phosphate, diamine hydrogen phosphate and phosphoric acid;

[0081] In an alternative embodiment, the sulfur source includes at least one of sulfur powder, sodium thiosulfate, ammonium sulfide, ammonium bisulfide, ammonium bisulfide and thioanisole;

[0082] In an optional embodiment, the mass ratio of the second pre-carbonized material to the second impurity element source is (99-70):(1-30);

[0083] In an optional embodiment, the second sintering temperature is 850°C-3000°C, and the time is 0.5h-12h;

[0084] In an optional embodiment, the second sintering is performed under a fifth protective atmosphere, and the fifth protective atmosphere includes at least one of nitrogen, argon, neon, helium, xenon and krypton;

[0085] In an optional embodiment, after the second pre-carbonization and before the second doping, a second pulverization process is further included;

[0086] In an optional embodiment, the median particle size of the pulverized material obtained by the second pulverization process is 2 μm-30 μm;

[0087] In an optional embodiment, the median particle size of the pulverized material obtained by the second pulverization process is 4 μm-20 μm;

[0088] In an optional embodiment, the median particle size of the pulverized material obtained by the second pulverization process is 5 μm-10 μm;

[0089] In an optional embodiment, after the second pulverization process and before the second doping process, a second purification process is further included;

[0090] In an optional embodiment, the second purification treatment comprises: mixing the material including the pulverized material, the second acid, and water, and then performing a first stirring, solid-liquid separation, washing the solid with water, and then performing a third drying;

[0091] In an optional embodiment, the second acid includes at least one of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid;

[0092] In an optional embodiment, the mass ratio of the pulverized material, the second acid, and the water is 1:(0.1-3):(5-10);

[0093] In an optional embodiment, the first stirring time is 1h-24h;

[0094] In an alternative embodiment, the endpoint pH of washing the solid with water is 4-7;

[0095] In an optional embodiment, the water is pure water or deionized water;

[0096] In an optional embodiment, the temperature of the third drying is 100°C-120°C, and the time is 24h-48h;

[0097] In an alternative embodiment, the oxidizing solution comprises an oxidizing acid and an oxidizing aid;

[0098] In an optional embodiment, the oxidizing acid includes at least one of concentrated sulfuric acid, concentrated nitric acid, concentrated phosphoric acid, perchloric acid and hypochlorous acid;

[0099] In an optional embodiment, the mass fraction of the concentrated sulfuric acid is not less than 60wt%, and the mass fraction of the concentrated nitric acid is not less than 50%;

[0100] In an optional embodiment, the oxidizing agent includes at least one of H2O2, (NH4)2S2O8, CrO3, and KMnO4;

[0101] In an optional embodiment, the mass ratio of the oxidizing acid to the oxidizing aid is 10:(0.1-2.0);

[0102] In an optional embodiment, the temperature of the oxidation expansion layer modification is 30°C-80°C, and the time is 1h-48h;

[0103] In an optional embodiment, after the oxidation expansion layer modification, after the material in the slurry settles, the supernatant is poured out, and the remaining slurry is diluted 5-10 times with water and centrifuged to obtain the fourth precursor;

[0104] In an optional embodiment, the centrifugation further comprises a third purification step: washing the solid obtained by the centrifugation with water;

[0105] In an optional embodiment, the end point of the washing is that the pH of the washing system is 6-7;

[0106] In an optional embodiment, the water is pure water or deionized water;

[0107] In an optional embodiment, the washing is followed by a fourth drying;

[0108] In an optional embodiment, the fourth drying is carried out at a temperature of 80° C. to 120° C. and for a time of 24 h to 48 h.

[0109] In an alternative embodiment, the intercalation reaction comprises:

[0110] Mixing materials including the fourth precursor, the alkaline additive and the reducing agent and performing a coating treatment to obtain a fifth precursor;

[0111] In an alternative embodiment, the alkaline additive includes at least one of a hydroxide, an oxide, a carbonate, a bicarbonate and a nitrate of sodium or potassium;

[0112] In an optional embodiment, the reducing agent includes a high molecular polymer and / or iron powder;

[0113] In an optional embodiment, the high molecular polymer includes at least one of starch, glucose, sucrose, fructose, natural rubber, phenolic resin, epoxy resin, melamine resin, polyfurfuryl alcohol, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin and polyacrylonitrile;

[0114] In an optional embodiment, the coating treatment includes: heating and stirring under a sixth protective atmosphere, cooling and discharging after heat preservation;

[0115] In an optional embodiment, the mass ratio of the fourth precursor, the alkaline additive and the reducing agent is (70-90): (20-8): (10-3);

[0116] In an optional embodiment, the heating and stirring speed is 30r / min-120r / min, the temperature is 300℃-850℃, the insulation time is 0.2h-1h, and the heating rate is 1℃ / min-5℃ / min;

[0117] In an optional embodiment, the coating treatment further includes a fourth purification: mixing the material obtained by the coating treatment, the third acid, and water, and then performing a second stirring, standing, washing, and a fifth drying to obtain the fifth precursor;

[0118] In an optional embodiment, the mass ratio of the material obtained by the coating treatment, the third acid, and the water is 1:(0.1-3):(5-10);

[0119] In an optional embodiment, the second stirring time is 1h-24h;

[0120] In an optional embodiment, the end point of the washing is that the pH of the washing system is 5-7;

[0121] In an optional embodiment, the water is pure water or deionized water;

[0122] In an optional embodiment, the fifth drying temperature is 100°C-120°C, and the time is 24h-48h;

[0123] In an optional embodiment, the fifth protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton;

[0124] In an optional embodiment, the post-treatment includes: subjecting the fifth precursor to a second heating treatment under a sixth protective atmosphere;

[0125] In an optional embodiment, the temperature of the second heating treatment is 300°C-1000°C, and the time is 0.5h-5h;

[0126] In an optional embodiment, the sixth protective atmosphere includes at least one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere and a krypton atmosphere.

[0127] The present application also provides a lithium-ion battery negative electrode, comprising the above-mentioned carbon negative electrode material.

[0128] The present application also provides a lithium ion battery, comprising the lithium ion battery negative electrode.

[0129] The present application also provides an electrical device, comprising the lithium-ion battery.

[0130] Compared with the prior art, the beneficial effects of this application include:

[0131] The carbon negative electrode material provided in the present application controls the distance between carbon layers, reduces the expansion rate, and improves the capacity by adding sodium and / or potassium elements between the carbon layers of the carbon matrix;

[0132] The preparation method of the carbon negative electrode material provided in the present application comprises the following steps: performing an intercalation reaction on a pre-treated carbon source and performing a post-treatment, adding sodium and / or potassium elements between carbon layers, controlling the distance between carbon layers, reducing the expansion rate, and increasing the capacity;

[0133] The lithium-ion battery negative electrode, lithium-ion battery and electrical equipment provided in the present application have good electrical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0134] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0135] Figure 1This is a SEM image of the carbon negative electrode material prepared in Example 1;

[0136] Figure 2 This is the XRD pattern of the carbon negative electrode material prepared in Example 1;

[0137] Figure 3 The first charge and discharge curves of the carbon negative electrode material and the first precursor prepared in Example 1;

[0138] Figure 4 A simplified flow chart of the carbon negative electrode material prepared in Examples 1-8;

[0139] Figure 5 This is a SEM image of the carbon negative electrode material prepared in Example 9;

[0140] Figure 6 A simplified flow chart of the preparation of carbon negative electrode materials for Examples 9-15;

[0141] Figure 7 Schematic diagram of the structure of the carbon negative electrode material prepared in Examples 9-15;

[0142] Figure 8 The charging time-charging SOC-voltage curve of the carbon negative electrode material obtained in Example 9 under 5C (CC+CV) conditions. DETAILED DESCRIPTION

[0143] As used herein:

[0144] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0145] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0146] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0147] In these examples, parts and percentages are by mass unless otherwise indicated.

[0148] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0149] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0150] The present application provides a carbon negative electrode material, which includes a carbon matrix and an alkali metal element. The alkali metal element is distributed between carbon layers of the carbon negative electrode material. The alkali metal element includes sodium and / or potassium. The carbon layer spacing of the carbon negative electrode material is 0.35nm-0.43nm.

[0151] In an optional embodiment, the carbon matrix is ​​doped with heteroelements;

[0152] In an optional embodiment, the heteroelement includes S and / or P;

[0153] It can be understood that the carbon skeleton is a network or surface structure formed by cross-linking of carbon atoms. The doping elements are doped into the carbon material to form covalent bonds with the carbon atoms on the skeleton. Due to the large volume of the doping elements, sub-nano pores exist in the gap between the doping elements and the carbon skeleton. The sub-nano pores provide a channel for the oxidizing solution to enter the interior of the carbon negative electrode material, thereby facilitating the oxidation expansion layer modification.

[0154] In some embodiments, the proportion of the impurity element to the total mass of the carbon negative electrode material is no more than 4%;

[0155] In some embodiments, the mass of the alkali metal element accounts for no more than 3% of the total mass of the carbon material;

[0156] and / or, the alkali metal element exists between the carbon layers in the form of ACx, wherein A is Na and / or K, and x>8;

[0157] Since the alkali metal (sodium / potassium) ion radius is larger than that of lithium ion, the alkali metal element (sodium and / potassium) between the carbon layers can increase the carbon layer spacing of the carbon negative electrode material and increase the lithium storage sites between the carbon layers. When X>8, the alkali metal element (sodium and / potassium) between the carbon layers only occupies a small amount of the carbon layer volume, thereby contributing a large amount of space between the carbon layers for lithium storage, and the resulting carbon negative electrode material exhibits a more excellent carbon layer lithium storage capacity performance.

[0158] In some embodiments, the specific surface area of ​​the carbon negative electrode material is 0.5 m 2 / g-10m 2 / g;

[0159] In some embodiments, the true density of the carbon negative electrode material is 1.8 g / cc-2.6 g / cc;

[0160] In some embodiments, the median particle size of the carbon negative electrode material is 2 μm-40 μm.

[0161] Optionally, the carbon layer spacing of the carbon negative electrode material can be 0.350nm, 0.355nm, 0.360nm, 0.365nm, 0.370nm, 0.375nm, 0.380nm, 0.385nm, 0.390nm, 0.395nm, 0.400nm, 0.405nm, 0.410nm, 0.415nm, 0.420nm, 0.425nm, 0.430nm and any value between 0.35nm-0.43; the specific surface area of ​​the carbon negative electrode material can be 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g, 3.5m 2 / g, 4m 2 / g, 4.5m 2 / g, 5m 2 / g, 5.5m 2 / g, 6m 2 / g, 6.5m 2 / g, 7m 2 / g, 7.5m 2 / g, 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g and 0.5m 2 / g-10m 2 / g, the true density can be 1.8g / cc, 1.9g / cc, 2.0g / cc, 2.1g / cc, 2.2g / cc, 2.3g / cc, 2.4g / cc, 2.5g / cc, 2.6g / cc and any value between 1.8g / cc-2.6g / cc, and the median particle size can be 2μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm and any value between 2μm-40μm.

[0162] The present application also provides a method for preparing a carbon negative electrode material, comprising:

[0163] The carbon source is subjected to pre-treatment, intercalation reaction and post-treatment in sequence to obtain the carbon negative electrode material.

[0164] In some embodiments, the pre-treatment comprises:

[0165] Performing a first pre-carbonization and a first sintering on the raw materials including the carbon source to obtain a first precursor;

[0166] Mixing and coating materials including the first precursor and a sacrificial carbon source, and then curing and oxidizing to obtain a second precursor;

[0167] In some embodiments, the carbon source comprises a hard carbon source, and the hard carbon source comprises at least one of phenolic resin, epoxy resin, melamine resin, furfural resin, acrylic resin, starch, glucose, sucrose, fructose, asphalt, almond shell, coconut shell, peach shell, walnut shell, jujube shell, polyfurfuryl alcohol, polyphenylene, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile;

[0168] In some embodiments, the first pre-carbonization temperature is 400°C-600°C, and the time is 0.5h-4h;

[0169] In some embodiments, after the first pre-carbonization and before the first sintering, a first pulverization process is further included;

[0170] In some embodiments, the median particle size of the pulverized material obtained by the first pulverization process is 2 μm-40 μm;

[0171] In some embodiments, the median particle size of the pulverized material obtained by the first pulverization process is 5 μm-20 μm;

[0172] In some embodiments, the median particle size of the pulverized material obtained by the first pulverization process is 6 μm-15 μm;

[0173] The purpose of crushing and controlling the median particle size is to control the contact area between the material particles. If the particles are too large, point contacts will be formed between the particles, the true density will decrease, the space utilization rate will decrease, and the final performance of the material will decrease. If the particles are too small, they will easily agglomerate, and subsequent mixed coating will make it difficult to achieve the ideal state of the sacrificial carbon source coating the first precursor, resulting in particle bonding rather than coating between the first precursor and the sacrificial carbon source.

[0174] Optionally, the temperature of the first pre-carbonization can be 400℃, 450℃, 500℃, 550℃, 600℃ and any value between 400℃-600℃, and the time can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h and any value between 0.5h-4h; the median particle size of the pulverized material obtained by the first pulverization treatment can be 2μm, 5μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm and any value between 2μm-40μm.

[0175] In some embodiments, a first purification process is further included after the pulverization process and before the sintering process.

[0176] In some embodiments, the first purification treatment comprises: mixing materials including the crushed material, the first acid and water, performing a first washing with water after immersion, and then performing a first drying;

[0177] In some embodiments, the first acid includes at least one of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, perchloric acid, acetic acid, and benzoic acid.

[0178] In some embodiments, the mass ratio of the pulverized material, the first acid and water is 1:(0.2-2):(5-10).

[0179] In some embodiments, the immersion time is 12h-48h.

[0180] In some embodiments, the material is washed with water to a pH of 6-7.

[0181] In some embodiments, the water is pure water or deionized water.

[0182] In some embodiments, the first drying is performed at a temperature of 80° C. to 120° C. for a time of 24 h to 48 h.

[0183] In some embodiments, after the first purification and before the first sintering, the method further includes: performing a first doping on the purified material using a first impurity element source;

[0184] In some embodiments, the first heteroelement source includes a phosphorus source and / or a sulfur source;

[0185] In some embodiments, the phosphorus source includes at least one of phosphorus pentoxide, phosphorus trioxide, ammonium phosphate, ammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphoric acid;

[0186] In some embodiments, the sulfur source includes at least one of sulfur powder, sodium thiosulfate, ammonium sulfide, ammonium bisulfide, ammonium bisulfide, and thioanisole;

[0187] In some embodiments, the mass ratio of the purified material to the first impurity element source is (99-70):(1-30);

[0188] In some embodiments, the sintering is performed under a first protective atmosphere.

[0189] In some embodiments, the first protective atmosphere comprises at least one of nitrogen, helium, neon, argon and krypton;

[0190] In some embodiments, the first sintering is performed at a temperature of 1000° C. to 1300° C. and for a time of 0.5 h to 12 h.

[0191] The purpose of the first purification treatment is to remove the impurity metal elements in the hard carbon source to ensure that the obtained hard carbon negative electrode material has good electrochemical performance during use. The sintering under the first protective atmosphere condition is mainly to prevent the hard carbon source from being oxidized.

[0192] Optionally, the mass ratio of the crushed material, the first acid and water can be any value between 1:0.2:5, 1:2:5, 1:0.2:10, 1:2:10, 1:1:6 and 1:(0.2-2):(5-10); the immersion time can be any value between 12h, 18h, 24h, 30h, 36h, 42h, 48h and 12h-48h; the pH end point of washing the material with water can be any value between 6, 6.5, 7 and 6-7; the first drying temperature can be any value between 80℃, 90℃, 100℃, 110℃, 120℃ and 80℃-120℃, and the time can be 24h , 30h, 36h, 48h and any value between 24h-48h; the mass ratio of the purified material to the first impurity element source can be 99:1, 95:5, 90:10, 85:15, 80:20, 75:25, 70:30 and any value between (99-70):(1-30); the temperature of the first sintering can be any value between 1000℃, 1100℃, 1200℃, 1300℃ and any value between 1000℃-1300℃, and the time can be any value between 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h and any value between 0.5h-12h.

[0193] In some embodiments, the sacrificial carbon source includes at least one of asphalt, glucose, sucrose, fructose, epoxy resin, phenolic resin, furfural resin, urea-formaldehyde resin, acrylic resin, polystyrene, polyvinyl alcohol, polyvinyl chloride, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile.

[0194] The selection of the sacrificial carbon source mainly considers its coating property on the first precursor and its reducing property on the active additive.

[0195] In some embodiments, the mass ratio of the sacrificial carbon source to the first precursor is (1-10): (99-90).

[0196] Optionally, the mass ratio of the sacrificial carbon source to the first precursor can be 1:99, 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, 9:91, 10:90 and any value between (1-5):(99-95).

[0197] In some embodiments, the mixed coating method includes solid phase mixed coating, liquid phase mixed coating and heating melt coating.

[0198] In some embodiments, the curing includes: heating and curing the mixed and coated material under a second protective atmosphere.

[0199] In some embodiments, the second protective atmosphere includes at least one of nitrogen, helium, neon, argon, and krypton.

[0200] In some embodiments, the temperature of the heating and curing is 100°C-300°C.

[0201] In some embodiments, the oxidation includes: heating the solidified material in an oxygen-containing atmosphere.

[0202] In some embodiments, the mass percentage of oxygen in the oxygen-containing atmosphere is 5%-100%.

[0203] In some embodiments, the oxygen-containing atmosphere is air.

[0204] In some embodiments, the temperature of the first heat treatment is 200°C-350°C, the heating rate is 0.5°C / min-5°C / min, and the holding time is 0.5h-3h.

[0205] In some embodiments, the oxidation is performed in an oxidation rotary kiln, and the rotation speed of the oxidation rotary kiln is 0.5r / min-2r / min.

[0206] The method of coating first, curing and then oxidizing is adopted in order to obtain a second precursor with the first precursor as the core and the porous sacrificial carbon source as the coating layer. Through air oxidation, the sacrificial carbon source coating layer of the first precursor produces a porous structure, which is conducive to the sacrificial carbon source coating layer and the active additive softened or melted at high temperature to fully contact, so that the two can fully react, which is conducive to the sodium and / or potassium generated by the reaction to infiltrate the surface of the hard carbon source material, and embed into the carbon layer of the hard carbon source material through self-discharge reaction during the high temperature and cooling stage.

[0207] Optionally, the temperature of the heating and curing can be 100°C, 200°C, 300°C and any value between 100°C and 300°C; the mass percentage of oxygen in the oxygen-containing atmosphere can be 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% and any value between 5% and 100%; the temperature of the first heat treatment can be 200°C, 250°C, 300°C, 350°C and any value between 200°C and 350°C, the heating temperature ... The temperature rate can be any value between 0.5℃ / min, 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min and 0.5℃ / min-5℃ / min, and the insulation time can be any value between 0.5h, 1h, 2h, 3h and 0.5h-3h; the rotation speed of the oxidation rotary kiln can be any value between 0.2r / min, 1r / min, 1.5r / min, 2r / min and 0.5r / min-2r / min.

[0208] In some embodiments, the intercalation reaction comprises:

[0209] Mixing materials including the second precursor and an active additive for providing sodium or potassium, heating for reaction, and then cooling to obtain the carbon negative electrode material;

[0210] In some embodiments, the active additive includes at least one of sodium hydroxide, sodium oxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium hyponitrite, sodium hypochlorite, sodium oxalate, sodium acetate, sodium amide, sodium ethoxide, potassium hydroxide, potassium oxide, potassium carbonate, potassium bicarbonate, potassium nitrate, potassium hyponitrite, potassium hypochlorite, potassium oxalate, potassium acetate, potassium amide and potassium ethoxide.

[0211] Sodium and potassium are selected to increase the spacing between carbon layers and increase the lithium storage sites between the carbon layers of the hard carbon negative electrode material, thereby improving the reversible capacity of the hard carbon negative electrode material; among the alkali metal elements, lithium itself does not have this property; sacrificial carbon sources are not sufficient to reduce rubidium, cesium, and francium, and the industrial applications of these three alkali metals are subject to various restrictions, such as cost, radioactivity, etc.

[0212] In some embodiments, the mass ratio of the second precursor to the active additive is 1:(0.5-2).

[0213] The amount of active additive used is calculated based on the amount of sodium and / or potassium elements embedded between the carbon layers. An excess of active additive is required to ensure that the sacrificial carbon source and the active additive mainly undergo a thermal reduction reaction rather than etching the sacrificial carbon source coating, thereby ensuring that the sacrificial carbon source is removed by the reaction and an alkali metal element is generated.

[0214] Optionally, the mass ratio of the second precursor to the active additive may be any value between 1:0.5, 1:1, 1:1.5, 1:2 and 1:(0.5-2).

[0215] In some embodiments, the particle size of the active additive is less than or equal to 30 mesh.

[0216] The active additives need to be sieved through a 30-mesh screen before use. If the active additives are in block form, they need to be crushed before use and then sieved through a 30-mesh screen; the crushing method is any one of air flow crushing and ball milling, or a combination of the two.

[0217] In some embodiments, the second precursor and the active additive are mixed using a VC machine, the rotation speed of the VC machine is 500 r / min-3000 r / min, and the mixing time is 5 min-40 min.

[0218] In some embodiments, the temperature of the heating reaction is 650°C-750°C, the heating rate is 0.5°C / min-5°C / min, and the insulation time is 20min-60min.

[0219] In some embodiments, the heating reaction is performed in a third protective atmosphere, and the third protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton.

[0220] In some embodiments, the cooling end point temperature is less than or equal to 120°C.

[0221] Optionally, the speed of the VC machine can be 500r / min, 1000r / min, 1500r / min, 2000r / min, 2500r / min, 3000r / min and any value between 500r / min-3000r / min, the mixing time can be 5min, 10min, 15min, 20min, 25min, 30min, 35min, 40min and any value between 5min-40min; the temperature of the heating reaction can be 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 770℃, 780℃, 790℃, 800℃, 810℃, 820℃, 830℃, 840℃, 850℃, 860℃, 870℃, 880℃, 890℃, 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, 960℃, 970℃, 980℃, 990℃, 1000℃, 1010℃, 1020℃, 1030℃, 1040℃, 1050℃, 1060℃, 1070℃, 1080℃, 1090℃, 1100℃, 1110℃, 1120℃, 1130℃, 1140℃, 1150℃, 1160℃, 1170℃, 1180℃, 1190℃ The temperature can be any value between 0℃, 760℃, 770℃, 780℃, 790℃, 800℃, 810℃, 820℃, 830℃, 840℃, 850℃ and 650℃-850℃. The heating rate can be any value between 0.5℃ / min, 1℃ / min, 1.5℃ / min, 2℃ / min, 2.5℃ / min, 3℃ / min, 3.5℃ / min, 4℃ / min, 4.5℃ / min, 5℃ / min and 0.5℃ / min-5℃ / min. The holding time can be any value between 20min, 30min, 40min, 50min, 60min and 20min-60min.

[0222] In some embodiments, the post-processing comprises:

[0223] The cooled material is mixed with water, washed until the pH is less than or equal to 10, then a neutralizing substance is added, filtered and washed until the pH is 6-7, and then a second drying is performed.

[0224] In some embodiments, the neutralizing substance includes at least one of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, perchloric acid, acetic acid, and benzoic acid.

[0225] In some embodiments, the second drying is performed at a temperature of 80° C. to 120° C. for a time of 24 h to 36 h.

[0226] The purpose of post-treatment is to remove unreacted active additives. The reactivity of alkali metal elements embedded in the carbon layer is greatly reduced, and it is difficult to react with water, acid, etc. Therefore, the active additives that do not participate in the reaction can be removed by acid washing to avoid affecting the production of battery poles and electrochemical test performance.

[0227] Optionally, the second drying temperature may be 80°C, 90°C, 100°C, 110°C, 120°C and any value between 80°C and 120°C, and the second drying time may be 24h, 30h, 36h and any value between 24h and 36h.

[0228] In some embodiments, the pre-treatment comprises:

[0229] performing a second pre-carbonization on the raw materials including the carbon source to obtain a third precursor;

[0230] Mixing materials including the third precursor and an oxidizing solution to perform oxidation expansion modification to obtain a fourth precursor;

[0231] In some embodiments, the second pre-carbonization is performed in a push plate kiln, a tube furnace or a box furnace;

[0232] In some embodiments, the carbon source includes a difficult-graphitizable carbon source and / or an easily-graphitizable carbon source;

[0233] In some embodiments, the non-graphitizable carbon source includes at least one of a natural biomass carbon source, a plant extract carbon source, and a polymer carbon source;

[0234] In some embodiments, the natural biomass carbon source includes at least one of coconut shell, almond shell, pistachio shell, macadamia shell, date shell, peanut shell, walnut shell, peach shell, cotton, gelatin, sawdust, bamboo, straw, kelp and lignin;

[0235] In some embodiments, the plant extract carbon source includes at least one of starch, glucose, sucrose, fructose and natural rubber;

[0236] In some embodiments, the polymer carbon source includes at least one of phenolic resin, epoxy resin, melamine resin, polyfurfuryl alcohol, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin and polyacrylonitrile;

[0237] In some embodiments, the graphitizable carbon source includes at least one of asphalt, petroleum coke, mesocarbon microbeads, and polyphenylene;

[0238] In some embodiments, the second pre-carbonization temperature is 400°C-700°C, and the time is 0.5h-10h;

[0239] Due to the high temperature, the carbon negative electrode material has a higher density, which can effectively overcome the subsequent etching of the carbon matrix by the oxidizing solution and alkaline additives, so as to ensure that the obtained carbon negative electrode material has a small specific surface area and a high initial charge and discharge efficiency.

[0240] Optionally, the temperature of the second pre-carbonization can be 400°C, 500°C, 600°C, 700°C and any value between 400°C and 700°C, and the time can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h and any value between 0.5h and 10h.

[0241] In some embodiments, the second pre-carbonization is performed under a fourth protective atmosphere, wherein the fourth protective atmosphere comprises at least one of nitrogen, argon, neon, helium, xenon, and krypton;

[0242] In some embodiments, after the second pre-carbonization, the method further comprises: performing a second doping on the second pre-carbonized material using a second impurity element source;

[0243] In some embodiments, the second doping includes: mixing the second pre-carbonized material with a second impurity element source, and performing a second sintering in an inert gas atmosphere;

[0244] In some embodiments, the second heteroelement source includes a phosphorus source and / or a sulfur source;

[0245] In some embodiments, the phosphorus source includes at least one of phosphorus pentoxide, phosphorus trioxide, ammonium phosphate, ammonium dihydrogen phosphate, diamine hydrogen phosphate, and phosphoric acid;

[0246] In some embodiments, the sulfur source includes at least one of sulfur powder, sodium thiosulfate, ammonium sulfide, ammonium bisulfide, ammonium bisulfide, and thioanisole;

[0247] In some embodiments, the mass ratio of the second pre-carbonized material to the second impurity element source is (99-70):(1-30);

[0248] In some embodiments, the second sintering temperature is 850°C-3000°C, and the time is 0.5h-12h;

[0249] After pre-carbonization and second doping, the doping group is doped into the carbon skeleton. Due to the large volume of the doping group, there are sub-nanometer micropores between the doping group and the carbon skeleton. After pre-carbonization, second doping and other steps, a third precursor doped with impurities with a dense structure and a large number of sub-nanometer micropores is obtained; the sub-nanometer micropores provide a channel for the oxidizing solution to enter the interior of the carbon negative electrode material. The oxidizing solution is used to oxidize and expand the carbon negative electrode material to obtain a fourth precursor with increased carbon layer spacing, which reduces the steric hindrance of sodium / potassium intercalation. The doping group is bonded to the carbon atom. Since the doping group has a large number of lone pairs of electrons, according to the inductive effect, the adjacent carbon atoms have a higher electron cloud density and carry a partial negative charge, which is opposite to the charge of the sodium / potassium ions, which enhances the power of sodium / potassium single substance to insert into the carbon layer, making sodium / potassium intercalation easy.

[0250] High-capacity and low-expansion carbon negative electrode materials can be prepared by utilizing the synergistic effect of heteroelement doping and sodium / potassium intercalation. It should be noted that: first, simple heteroelement doping makes carbon atoms carry partial negative charge and improves capacity; but simple heteroelement doping does not change the carbon interlayer spacing, and the expansion and cycle performance of the resulting carbon negative electrode material decreases as the capacity performance increases; secondly, simple sodium / potassium intercalation modification improves the carbon interlayer spacing of the carbon negative electrode material, increases the lithium storage sites between the carbon layers, and reduces the charging and discharging lithium ion diffusion impedance, thereby improving the capacity, rate, and expansion performance of the carbon negative electrode material; however, the carbon negative electrode material prepared by simple sodium / potassium intercalation modification, in a high temperature environment and during the cycle, the intercalated sodium / potassium elements are easily detached from the carbon negative electrode material, resulting in capacity, expansion, and high-temperature performance attenuation. The doping of heteroelements enables the sodium / potassium elements to exist stably in the carbon negative electrode material through the induction effect, while the sodium / potassium intercalation creates a buffer space for the volume expansion of the heteroelement doped carbon negative electrode material during the charging and discharging process by expanding the distance between carbon layers. The two work together to prepare a high-capacity, low-expansion carbon, high-temperature resistant and long-life carbon negative electrode material.

[0251] In some embodiments, the second sintering is performed under a fifth protective atmosphere, wherein the fifth protective atmosphere includes at least one of nitrogen, argon, neon, helium, xenon, and krypton;

[0252] Optionally, the mass ratio of the second pre-carbonized material to the impurity element source can be 99:1, 95:5, 90:10, 85:15, 80:20, 75:25, 70:30 and any value between (99-70):(1-30); the second sintering temperature can be 850℃, 1000℃, 1500℃, 2000℃, 2500℃, 3000℃ and any value between 850℃-3000℃, and the time can be 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h and any value between 0.5h-12h.

[0253] In some embodiments, after the second pre-carbonization and before the second doping, a second pulverization process is further included;

[0254] In some embodiments, the median particle size of the pulverized material obtained by the second pulverization process is 2 μm-30 μm;

[0255] In some embodiments, the median particle size of the pulverized material obtained by the second pulverization process is 4 μm-20 μm;

[0256] In some embodiments, the median particle size of the pulverized material obtained by the second pulverization process is 5 μm-10 μm;

[0257] Optionally, the median particle size of the pulverized material obtained by the second pulverization treatment may be 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm and any value between 2 μm and 30 μm.

[0258] In some embodiments, after the second pulverization process and before the second doping process, a second purification process is further included;

[0259] In some embodiments, the second purification treatment comprises: mixing the material including the pulverized material, the second acid, and water, and then performing a first stirring, solid-liquid separation, washing the solid with water, and then performing a third drying;

[0260] In some embodiments, the second acid comprises at least one of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid, and sulfuric acid;

[0261] In some embodiments, the mass ratio of the pulverized material, the second acid, and the water is 1:(0.1-3):(5-10);

[0262] In some embodiments, the first stirring time is 1h-24h;

[0263] In some embodiments, the endpoint pH of washing the solid with water is 4-7;

[0264] In some embodiments, the water is pure water or deionized water;

[0265] In some embodiments, the third drying is performed at a temperature of 100°C to 120°C and for a time of 24h to 48h;

[0266] Optionally, the mass ratio of the crushed material, the second acid and the water can be any value between 1:0.1:5, 1:1:5, 1:3:5, 1:0.1:8, 1:1:8, 1:3:8, 1:0.1:10, 1:1:10, 1:3:10 and 1:(0.1-3):(5-10); the time of the first stirring can be any value between 1h, 6h, 12h, 18h, 24h and 1h-24h; the endpoint pH of washing the solid with water can be any value between 4, 5, 6, 7 and 4-7; the temperature of the third drying can be any value between 100℃, 110℃, 120℃ and 100℃-120℃, and the time can be any value between 24h, 30h, 36h, 42h, 48h and 24h-48h.

[0267] In some embodiments, the oxidizing solution includes an oxidizing acid and an oxidizing aid;

[0268] In some embodiments, the oxidizing acid comprises at least one of concentrated sulfuric acid, concentrated nitric acid, concentrated phosphoric acid, perchloric acid, and hypochlorous acid;

[0269] In some embodiments, the mass fraction of the concentrated sulfuric acid is not less than 60wt%, and the mass fraction of the concentrated nitric acid is not less than 50%;

[0270] In some embodiments, the oxidizing agent includes at least one of H2O2, (NH4)2S2O8, CrO3, and KMnO4;

[0271] In some embodiments, the mass ratio of the oxidizing acid to the oxidizing aid is 10:(0.1-2.0);

[0272] In some embodiments, the temperature of the oxidation expansion layer modification is 30°C-80°C, and the time is 1h-48h;

[0273] Optionally, the mass ratio of the oxidizing acid to the oxidizing aid can be any value between 10:0.1, 10:0.5, 10:1.0, 10:1.5, 10:2.0 and 10:(0.1-2.0); the temperature of the oxidative expansion layer modification can be any value between 30°C, 40°C, 50°C, 60°C, 70°C, 80°C and 30°C-80°C, and the time can be any value between 1h, 6h, 12h, 18h, 24h, 30h, 36h, 42h, 48h and 1h-48h.

[0274] In some embodiments, after the oxidation expansion layer modification, after the material in the slurry settles, the supernatant is poured out, and the remaining slurry is diluted 5-10 times with water and centrifuged to obtain the fourth precursor;

[0275] In some embodiments, the centrifugation further comprises a third purification step: washing the solid matter obtained by the centrifugation with water;

[0276] In some embodiments, the end point of the washing is when the pH of the washing system is 6-7;

[0277] In some embodiments, the water is pure water or deionized water;

[0278] In some embodiments, the washing is followed by a fourth drying;

[0279] In some embodiments, the fourth drying is performed at a temperature of 80° C. to 120° C. for a time of 24 h to 48 h.

[0280] Optionally, the fourth drying temperature may be 80°C, 90°C, 100°C, 110°C, 120°C and any value between 80°C and 120°C, and the time may be 24h, 30h, 36h, 42h, 48h and any value between 24h and 48h.

[0281] In some embodiments, the intercalation reaction comprises:

[0282] Mixing materials including the fourth precursor, the alkaline additive and the reducing agent and performing a coating treatment to obtain a fifth precursor;

[0283] In some embodiments, the base additive includes at least one of a hydroxide, oxide, carbonate, bicarbonate, and nitrate of sodium or potassium;

[0284] In some embodiments, the reducing agent includes a high molecular weight polymer and / or iron powder;

[0285] In some embodiments, the high molecular polymer includes at least one of starch, glucose, sucrose, fructose, natural rubber, phenolic resin, epoxy resin, melamine resin, polyfurfuryl alcohol, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin and polyacrylonitrile;

[0286] In some embodiments, the coating treatment includes: heating and stirring under a sixth protective atmosphere, cooling and discharging after heat preservation;

[0287] In some embodiments, the mass ratio of the fourth precursor, the base additive and the reducing agent is (70-90): (20-8): (10-3);

[0288] In some embodiments, the heating stirring speed is 30r / min-120r / min, the temperature is 300℃-850℃, the insulation time is 0.2h-1h, and the heating rate is 1℃ / min-5℃ / min;

[0289] Optionally, the mass ratio of the fourth precursor, the alkali additive and the reducing agent can be any value between 70:20:10, 80:10:10, 89:8:3 and (70-90):(20-8):(10-3); the heating and stirring speed can be 30r / min, 40r / min, 50r / min, 60r / min, 70r / min, 80r / min, 90r / min, 100r / min, 110r / min, 120r / min and any value between 30r / min-120r / min, the temperature can be 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, 850℃ and any value between 300℃-850℃, the holding time can be 0.2h, 0.5h, 1h and any value between 0.2h-1h, and the heating rate can be 1℃ / min, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min and any value between 1℃ / min-5℃ / min.

[0290] The alkaline additives are reduced to sodium / potassium elements through thermal reduction reaction, and sodium / potassium is intercalated into the carbon interlayers through self-discharge.

[0291] In some embodiments, the coating treatment further includes a fourth purification: mixing materials including the material obtained by the coating treatment, the third acid, and water, and then performing a second stirring, standing, washing, and a fifth drying to obtain the fifth precursor;

[0292] In some embodiments, the mass ratio of the material obtained by the coating process, the third acid, and the water is 1:(0.1-3):(5-10);

[0293] In some embodiments, the second stirring time is 1h-24h;

[0294] In some embodiments, the end point of the washing is when the pH of the washing system is 5-7;

[0295] In some embodiments, the water is pure water or deionized water;

[0296] In some embodiments, the fifth drying is performed at a temperature of 100°C to 120°C and for a time of 24h to 48h;

[0297] Optionally, the mass ratio of the material obtained by the coating treatment, the third acid and the water can be any value between 1:0.1:5, 1:1:5, 1:3:5, 1:0.1:8, 1:1:8, 1:3:8, 1:0.1:10, 1:1:10, 1:3:10 and 1:(0.1-3):(5-10); the time of the second stirring can be any value between 1h, 6h, 12h, 18h, 24h and 1h-24h; the end point of the washing is that the pH of the washing system can be any value between 5, 6, 7 and 5-7; the temperature of the fifth drying can be any value between 100℃, 110℃, 120℃ and 100℃-120℃, and the time can be any value between 24h, 30h, 36h, 42h, 48h and 24h-48h.

[0298] In some embodiments, the fifth protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton;

[0299] In some embodiments, the post-processing includes: subjecting the fifth precursor to a second heating treatment under a sixth protective atmosphere;

[0300] In some embodiments, the temperature of the second heating treatment is 300°C-1000°C, and the time is 0.5h-5h;

[0301] In some embodiments, the sixth protective atmosphere includes at least one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere, and a krypton atmosphere.

[0302] High temperature treatment improves the uniformity of sodium / potassium distribution to ensure a high initial efficiency of the carbon negative electrode without significantly reducing the spacing between carbon layers.

[0303] Optionally, the temperature of the second heat treatment can be 300℃, 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃ and any value between 300℃-1000℃, and the time can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h and any value between 0.5h-5h.

[0304] The present application also provides a lithium-ion battery negative electrode, comprising the above-mentioned carbon negative electrode material.

[0305] The present application also provides a lithium ion battery, comprising the lithium ion battery negative electrode.

[0306] The present application also provides an electrical device, comprising the lithium-ion battery.

[0307] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0308] Example 1

[0309] The phenolic resin (Jining Huakai Resin Co., Ltd., PR-56052) was pre-carbonized at 500°C for 0.5h under the protection of a nitrogen atmosphere, and the carbonized material with a median particle size of about 9μm was obtained by air flow crushing. The carbonized material, hydrochloric acid, and deionized water were mixed in a mass ratio of 1:0.5:5, and after being immersed for 24h, the material was washed with deionized water to a pH of 6-7, and centrifuged and dried; then, it was sintered at 1000°C for 1h in a box furnace under the protection of a nitrogen atmosphere, and cooled to room temperature to obtain a first precursor.

[0310] According to the mass ratio of the first precursor to phenolic resin of 97:3, phenolic resin was weighed, dissolved in ethanol solvent, and stirred evenly to prepare a 5wt% phenolic resin ethanol solution, and then the first precursor was added under stirring, and stirred at 600r / min for 30min using a high-speed disperser, and the obtained mixed slurry was spray dried, and the obtained powder was transferred to a box furnace, and cured at 150°C for 10h under nitrogen atmosphere protection, cooled to room temperature, and the obtained material was put into an oxidation rotary furnace, and air was introduced at a flow rate of 200L / h. The speed was controlled at 1r / min, and the temperature was increased to 250°C at a heating rate of 2°C / min, kept warm for 1h, and then cooled to room temperature to obtain a second precursor.

[0311] According to the mass ratio of the second precursor to potassium hydroxide of 1:0.5, the two are mixed evenly, transferred to a box furnace under the protection of a nitrogen atmosphere, heated to 700°C, kept warm for 60 minutes, cooled to room temperature and transferred to a container, deionized water is added and stirred into a slurry, washed with deionized water until the pH is less than or equal to 10, and then excess hydrochloric acid is added, stirred, filtered, washed to pH = 6-7, transferred to a 120°C oven and dried for more than 24 hours to obtain a hard carbon negative electrode material.

[0312] The SEM image of the carbon negative electrode material obtained in Example 1 is as follows Figure 1 As shown, the XRD pattern is Figure 2 As shown, the first charge and discharge curves of the hard carbon negative electrode material and the first precursor are as follows Figure 3 As shown. Figure 3It can be seen that the release capacity of the hard carbon negative electrode material obtained in Example 1 is higher than that of the first precursor, the capacity of the platform area is equivalent to the latter, and the capacity of the slope area is higher than the latter. The slope area is the lithium storage capacity between carbon layers, and the platform area corresponds to the lithium storage between microcrystalline gaps. This shows that potassium is embedded in the carbon layers of the hard carbon negative electrode material through self-discharge, resulting in an increase in the hard carbon layer spacing and an increase in interlayer lithium storage sites.

[0313] Example 2

[0314] The coconut shell (produced in Hainan Province, China) was pre-carbonized at 400°C for 2 hours under a nitrogen atmosphere, and the carbonized material with a median particle size of about 6 μm was obtained by air flow crushing. The carbonized material, hydrochloric acid, and deionized water were mixed in a mass ratio of 1:1:10, and after being immersed for 48 hours, it was washed with deionized water to a pH of 6-7, centrifuged and dried, and sintered at 1050°C in a box furnace under a nitrogen atmosphere for 1 hour, and cooled to room temperature to obtain a first precursor.

[0315] According to the mass ratio of the first precursor: epoxy resin (Jinan Shengquan Group Co., Ltd., SQCN700 epoxy resin) of 97:3, the epoxy resin was weighed and dissolved in THF (tetrahydrofuran) solvent, and stirred evenly to prepare a 5wt% epoxy resin THF solution, and then the first precursor was added under stirring, and a high-speed disperser was used to stir at a speed of 550r / min for 60min, and the mixed slurry was added to a water bath for evaporation under stirring, and transferred to an oven at 100°C and dried for 24h to obtain a dry powder, which was then transferred to a box furnace and cured at 200°C for 15h under nitrogen atmosphere protection, cooled to room temperature, and the obtained material was put into an oxidation rotary furnace, air was introduced with a flow rate of 400L / h, the speed was controlled at 2r / min, the temperature was increased to 300°C at a heating rate of 3°C / min, kept warm for 0.5h, and then cooled to room temperature to obtain a second precursor.

[0316] Mix the second precursor and sodium oxide in a mass ratio of 1:1, transfer them to a box furnace, heat them to 750°C under a nitrogen atmosphere, keep them warm for 30 minutes, cool them to room temperature, transfer them to a container, add deionized water and stir them into a slurry, wash them with deionized water until the pH is less than 10, then add an excess of 50wt% sulfuric acid, stir, filter, wash until the pH is 6-7, transfer them to a 120°C oven and bake them for more than 24 hours to obtain a hard carbon negative electrode material.

[0317] Example 3

[0318] The asphalt was put into an oxidation rotary furnace and oxidized at 250°C for 2 hours. After cooling, it was crushed and transferred to a box furnace. It was pre-carbonized at 600°C for 4 hours under an argon atmosphere. The carbonized material was crushed by air flow to obtain a carbonized material with a median particle size of about 12 μm. The carbonized material, hydrochloric acid and deionized water were mixed in a mass ratio of 1:1:10. After being immersed for 48 hours, it was washed with deionized water to a pH of 6-7, centrifuged and dried, and sintered at 1300°C for 3 hours in a box furnace under an argon atmosphere. It was cooled to room temperature to obtain a first precursor.

[0319] Sucrose is weighed according to the mass ratio of the first precursor to sucrose of 95:5, dissolved in deionized water, and stirred evenly to prepare a 4wt% sucrose aqueous solution, and then the first precursor is added under stirring, and a high-speed disperser is used to stir at a speed of 600r / min for 60min, and the mixed slurry is spray-dried; then transferred to a box furnace, cured at 180°C for 2h under a nitrogen atmosphere, cooled to room temperature, and the obtained material is put into an oxidation rotary kiln, air is introduced at a flow rate of 400L / h, the speed is controlled at 0.5r / min, the temperature is increased to 350°C at a heating rate of 3°C / min, kept warm for 0.5h, and then cooled to room temperature to obtain a second precursor.

[0320] Mix the second precursor and potassium carbonate in a mass ratio of 1:2, transfer them to a box furnace, heat them to 750°C in an argon atmosphere, keep them warm for 30 minutes, cool them to room temperature, transfer them to a container, add deionized water and stir them into a slurry, wash them with deionized water until the pH is less than 10, then add an excess of 10wt% nitric acid, stir, filter, wash until the pH is 6-7, transfer them to a 120°C oven and bake them for more than 24 hours to obtain a hard carbon negative electrode material.

[0321] Example 4

[0322] Potato starch (produced in Inner Mongolia, China) was placed in a box furnace, heated to 220°C for 6 hours under nitrogen atmosphere protection, and then heated to 550°C for pre-carbonization for 4 hours, and air flow crushed to obtain a carbonized material with a median particle size of about 10 μm, and the carbonized material, hydrochloric acid, and deionized water were mixed in a mass ratio of 1:1:10, and then immersed for 48 hours and washed with deionized water to pH = 6-7, centrifuged and dried, and sintered at 1050°C for 2 hours in a graphitization furnace under argon atmosphere protection, and cooled to room temperature to obtain a first precursor;

[0323] Weigh asphalt according to the mass ratio of the first precursor to asphalt of 96:4, then put the first precursor and asphalt into the VC heating furnace, set the speed to 120r / min under nitrogen atmosphere, heat to 250℃ at 2℃ / min under stirring, keep for 1h, and then cool to room temperature. Then transfer to a box furnace, cure at 300℃ for 3h under nitrogen atmosphere, cool to room temperature, break up VC, put the obtained material into an oxidation rotary kiln, let in air, the flow rate is 400L / h, the speed is controlled at 0.5r / min, heat to 200℃ at a heating rate of 1℃ / min, keep warm for 2h, and then cool to room temperature to obtain the second precursor;

[0324] According to the mass ratio of the second precursor: sodium hydroxide of 1:1.2, the two are mixed evenly, transferred to a box furnace, heated to 720°C in an argon atmosphere, kept warm for 60 minutes, cooled to room temperature and transferred to a container, deionized water is added and stirred into a slurry, washed with deionized water until the pH is less than 10, and then an excess of 10wt% hydrochloric acid is added, stirred, filtered, and washed until the pH is 6-7, transferred to a 120°C oven and dried for more than 24 hours to obtain a hard carbon negative electrode material.

[0325] Example 5

[0326] Sucrose (produced in Guangdong, China) was placed in a box furnace, heated to 180°C for 6 hours under nitrogen atmosphere protection, and then heated to 550°C for pre-carbonization for 5 hours, and air flow crushed to obtain a carbonized material with a median particle size of about 11 μm, and the carbonized material, hydrochloric acid, and deionized water were mixed in a mass ratio of 1:0.4:5, and then immersed for 48 hours and washed with deionized water to pH = 6-7, centrifuged and dried, and sintered at 1100°C for 3 hours in a tubular furnace under helium atmosphere protection, and cooled to room temperature to obtain a first precursor;

[0327] Weigh polyaniline according to the mass ratio of the first precursor to polyaniline of 96:4, then put the first precursor and polyaniline into a VC machine, rotate at 400 rpm / min, mix for 20 minutes, then transfer to a box furnace, cure at 150°C for 3 hours under a helium atmosphere, cool to room temperature, break up the VC, put the resulting material into an oxidation rotary furnace, introduce air at a flow rate of 300 L / h, control the speed at 1 r / min, heat to 200°C at a heating rate of 5°C / min, keep warm for 2 hours, and then cool to room temperature to obtain a second precursor;

[0328] Mix the second precursor and potassium bicarbonate in a mass ratio of 1:1.5, transfer them to a box furnace, heat them to 850°C in an argon atmosphere, keep them warm for 60 minutes, cool them to room temperature, transfer them to a container, add deionized water and stir them into a slurry, wash them with deionized water until the pH is less than 10, then add an excess of 20wt% hydrochloric acid, stir, filter, wash until the pH is 6-7, transfer them to a 120°C oven and bake them for more than 24 hours to obtain a hard carbon negative electrode material.

[0329] Example 6

[0330] Epoxy resin and ethylenediamine were mixed in a mass ratio of 8:2, placed in a box furnace, heated to 120°C for 24 hours under nitrogen atmosphere, and then heated to 600°C for pre-carbonization for 4 hours, and air flow crushed to obtain a carbonized material with a median particle size of about 8 μm, and the carbonized material, sulfuric acid, and deionized water were mixed in a mass ratio of 1:0.4:7, and then immersed for 24 hours and washed with deionized water to pH = 6-7, centrifuged and dried, and sintered at 1050°C for 2 hours in a tubular furnace under helium atmosphere, and cooled to room temperature to obtain a first precursor;

[0331] The first precursor and glucose were put into a VC machine at a mass ratio of 90:10, with a rotation speed of 500 rpm / min, mixed for 30 minutes, and then transferred to a box furnace, solidified at 150°C for 5 hours under a helium atmosphere, cooled to room temperature, and the VC was broken up. The resulting material was put into an oxidation rotary furnace, and air was introduced at a flow rate of 300 L / h. The rotation speed was controlled at 1 r / min, and the temperature was increased to 200°C at a heating rate of 5°C / min. The temperature was kept for 2 hours, and then cooled to room temperature to obtain a second precursor;

[0332] Mix the second precursor and potassium bicarbonate in a mass ratio of 1:1.5, transfer them to a box furnace, heat them to 850°C in an argon atmosphere, keep them warm for 60 minutes, cool them to room temperature, transfer them to a container, add deionized water and stir them into a slurry, wash them with deionized water until the pH is less than 10, then add an excess of 20wt% hydrochloric acid, stir, filter, wash until the pH is 6-7, transfer them to a 120°C oven and bake them for more than 24 hours to obtain a hard carbon negative electrode material.

[0333] Example 7

[0334] The phenolic resin (Jining Huakai Resin Co., Ltd., PR-56052) was pre-carbonized at 550°C for 2h under nitrogen atmosphere protection, and air flow crushed to obtain a carbonized material with a median particle size of about 7μm. The carbonized material, hydrochloric acid, and deionized water were mixed in a mass ratio of 1:1:8, and after impregnation for 24h, the material was washed with deionized water to a pH of 6-7, and centrifuged and dried; then, it was sintered at 1000°C for 3h in a box furnace under nitrogen atmosphere protection, and cooled to room temperature to obtain a first precursor.

[0335] According to the mass ratio of the first precursor to phenolic resin of 97:3, phenolic resin was weighed, dissolved in ethanol solvent, and stirred evenly to prepare a 5wt% phenolic resin ethanol solution, and then the first precursor was added under stirring, and stirred at 600r / min for 30min using a high-speed disperser, and the obtained mixed slurry was spray dried, and the obtained powder was transferred to a box furnace, and cured at 150°C for 10h under nitrogen atmosphere protection, cooled to room temperature, and the obtained material was put into an oxidation rotary furnace, and air was introduced at a flow rate of 200L / h. The speed was controlled at 1r / min, and the temperature was increased to 250°C at a heating rate of 2°C / min, kept warm for 1h, and then cooled to room temperature to obtain a second precursor.

[0336] According to the mass ratio of the second precursor, potassium hydroxide and sodium hydroxide of 1:0.3:0.2, the three are mixed evenly, transferred to a box furnace under the protection of a nitrogen atmosphere, heated to 700°C, kept warm for 60 minutes, cooled to room temperature and transferred to a container, deionized water is added and stirred into a slurry, washed with deionized water until the pH is less than or equal to 10, and then excess hydrochloric acid is added, stirred, filtered, washed to pH = 6-7, transferred to a 120°C oven and dried for more than 24 hours to obtain a hard carbon negative electrode material.

[0337] Example 8

[0338] The phenolic resin (Jining Huakai Resin Co., Ltd., PR-56052) was pre-carbonized at 500°C for 0.5h under nitrogen atmosphere protection, and air flow crushed to obtain a carbonized material with a median particle size of about 9μm. The carbonized material, hydrochloric acid, and deionized water were mixed in a mass ratio of 1:0.5:5, and after immersion for 24h, the material was washed with deionized water to a pH of 6-7, and centrifuged and dried; the dried carbonized material and phosphorus pentoxide were mixed in a ratio of 95:5 VC, and then sintered at 1000°C for 1h in a box furnace under nitrogen atmosphere protection, and cooled to room temperature to obtain a first precursor.

[0339] According to the mass ratio of the first precursor to phenolic resin of 97:3, phenolic resin was weighed, dissolved in ethanol solvent, and stirred evenly to prepare a 5wt% phenolic resin ethanol solution, and then the first precursor was added under stirring, and stirred at 600r / min for 30min using a high-speed disperser, and the obtained mixed slurry was spray dried, and the obtained powder was transferred to a box furnace, and cured at 150°C for 10h under nitrogen atmosphere protection, cooled to room temperature, and the obtained material was put into an oxidation rotary furnace, and air was introduced at a flow rate of 200L / h. The speed was controlled at 1r / min, and the temperature was increased to 250°C at a heating rate of 2°C / min, kept warm for 1h, and then cooled to room temperature to obtain a second precursor.

[0340] According to the mass ratio of the second precursor to potassium hydroxide of 1:0.5, the two are mixed evenly, transferred to a box furnace under the protection of a nitrogen atmosphere, heated to 700°C, kept warm for 60 minutes, cooled to room temperature and transferred to a container, deionized water is added and stirred into a slurry, washed with deionized water until the pH is less than or equal to 10, and then excess hydrochloric acid is added, stirred, filtered, washed to pH = 6-7, transferred to a 120°C oven and dried for more than 24 hours to obtain a hard carbon negative electrode material.

[0341] The preparation process diagram of Examples 1-8 is as follows Figure 4 shown.

[0342] The hard carbon negative electrode material provided by the present application is obtained by distributing sodium and / or potassium elements between the carbon layers of the hard carbon negative electrode material. Since the ionic radius of sodium / potassium is larger than that of lithium ions, the carbon layer spacing of the hard carbon negative electrode material is significantly expanded after sodium and / or potassium is embedded, thereby increasing the lithium storage sites between the carbon layers of the hard carbon negative electrode material and improving the reversible capacity of the hard carbon negative electrode material. It not only has a higher energy density, but also improves the carbon layer spacing of the hard carbon, which can reduce the internal resistance of lithium ion diffusion and obtain good fast charging performance. At the same time, since the expanded carbon layer spacing is conducive to reducing the volume expansion during the lithium insertion process, the expansion rate of the obtained hard carbon negative electrode material is low.

[0343] The preparation method of the hard carbon negative electrode material provided in the present application obtains a first precursor by pre-carbonizing and sintering the hard carbon source, and obtains a dense structure, so that the first precursor does not react with the active additive, thereby ensuring that the specific surface area of ​​the hard carbon negative electrode material obtained after the subsequent heating reaction does not change significantly, and finally the irreversible capacity corresponding to the SEI film (the electrode material and the electrolyte react at the solid-liquid interface to form a passivation film covering the surface of the electrode material) generated during use does not increase significantly, and the first efficiency is high; the sacrificial carbon source is coated on the first precursor, and then cured and oxidized to obtain a porous sacrificial carbon source coating layer The second precursor undergoes a reduction reaction during the subsequent heating reaction, and the sacrificial carbon source is consumed. The molten sodium and / or potassium generated after the reaction of the active additives fully infiltrate the surface of the material. During the insulation and cooling stages, the sodium and / or potassium elements, through their self-discharge characteristics, donate electrons to carbon atoms and are embedded in the carbon interlayers of the hard carbon negative electrode material in a cationic state. After embedding, they seize the electrons of the carbon atoms and restore the atomic state. The embedding of sodium and / or potassium expands the distance between carbon layers, increases the lithium storage sites between carbon layers of the hard carbon negative electrode material, and improves the reversible capacity of the hard carbon. This method is also easy to operate, has a variety of optional carbon sources, and has mild conditions suitable for large-scale production.

[0344] Comparative Example 1

[0345] Phenolic resin: potassium hydroxide are mixed evenly according to a mass ratio of 7:1, and the two are transferred to a box furnace. Under an argon atmosphere, they are first cured at 150°C for 3 hours, then pre-sintered at 650°C for 30 minutes, and then heated to 1000°C for sintering for 2 hours. After cooling to room temperature, the mixture is transferred to a container, deionized water is added and stirred to form a slurry, and the mixture is washed with deionized water until the pH is less than 10. Then, excess hydrochloric acid is added, stirred, filtered, and washed until the pH is 6-7. The mixture is transferred to a 120°C oven and dried for more than 24 hours. After drying, the mixture is air flow-pulverized to a median particle size of about 9 μm to obtain a hard carbon negative electrode material.

[0346] Comparative Example 2

[0347] The thermosetting phenolic resin was pre-carbonized at 500°C for 0.5h under nitrogen atmosphere protection, and air flow crushed to obtain a carbonized material with a median particle size of about 9μm. The carbonized material, hydrochloric acid, and deionized water were mixed in a mass ratio of 1:0.5:5, and after immersion for 24h, it was washed with deionized water to pH=6-7, and centrifuged and dried to obtain a first precursor.

[0348] According to the mass ratio of the first precursor to the phenolic resin of 97:3, the phenolic resin is weighed, dissolved in an ethanol solvent, and stirred to prepare a 5wt% phenolic resin ethanol solution, and then the first precursor is added under stirring; a high-speed disperser is used to stir at a speed of 600r / min for 30min, and the obtained mixed slurry is spray-dried, and the obtained powder is transferred to a box furnace, and cured at 150°C for 10h under the protection of a nitrogen atmosphere, and cooled to room temperature; the obtained material is put into an oxidation rotary furnace, air is introduced at a flow rate of 200L / h, the speed is controlled at 1r / min, the temperature is increased to 250°C at a heating rate of 2°C / min, and the temperature is kept for 1h, and then cooled to room temperature to obtain a second precursor;

[0349] According to the mass ratio of the second precursor: potassium hydroxide of 1:0.5, the two are mixed evenly, transferred to a box-type furnace, heated to 700°C under the protection of a nitrogen atmosphere, kept warm for 60 minutes, cooled to room temperature, transferred to a container, added with deionized water and stirred into a slurry, washed with deionized water until the pH is less than 10, and then added with excess hydrochloric acid, stirred, filtered, and washed until the pH is 6-7, transferred to a 120°C oven and baked for more than 24 hours until dry; then transferred to a box-type furnace, heated to 1000°C under an argon atmosphere and sintered for 2 hours, the VC was broken up, cooled to room temperature, and a hard carbon negative electrode material was obtained.

[0350] Comparative Example 3

[0351] The thermosetting phenolic resin was pre-carbonized at 500°C for 0.5h under nitrogen atmosphere, and air flow crushed to obtain a carbonized material with a median particle size of about 9μm. The carbonized material: hydrochloric acid: deionized water were mixed in a mass ratio of 1:0.5:5, immersed for 24h, washed with deionized water to pH=6-7, centrifuged and dried, sintered at 1000°C for 1h in a box furnace under nitrogen atmosphere, cooled to room temperature, and the obtained material was put into an oxidation rotary furnace, air was introduced at a flow rate of 200L / h, the speed was controlled at 1r / min, the temperature was increased to 250°C at a heating rate of 2°C / min, kept warm for 1h, and then cooled to room temperature to obtain a first precursor.

[0352] Mix the first precursor and potassium hydroxide in a mass ratio of 1:0.5, transfer them to a box furnace, heat them to 700°C under a nitrogen atmosphere, keep them warm for 60 minutes, cool them to room temperature, transfer them to a container, add deionized water and stir them into a slurry, wash them with deionized water until the pH is less than 10, then add excess hydrochloric acid, stir, filter, wash until the pH is 6-7, transfer them to a 120°C oven and bake them for more than 24 hours to obtain a hard carbon negative electrode material.

[0353] Comparative Example 4

[0354] The thermosetting phenolic resin was pre-carbonized at 500°C for 0.5h under a nitrogen atmosphere, and air flow crushed to obtain a carbonized material with a median particle size of about 9μm. The carbonized material: hydrochloric acid: deionized water were mixed in a mass ratio of 1:0.5:5, and after being immersed for 24h, it was washed with deionized water to a pH of 6-7, centrifuged and dried, and sintered at 1000°C for 1h in a box furnace under a nitrogen atmosphere, and cooled to room temperature to obtain a first precursor.

[0355] The thermosetting phenolic resin was cured at 150° C. for 10 h under nitrogen atmosphere, cooled to room temperature, and then ball-milled to a particle size of about 20 μm, and passed through a 200-mesh sieve to obtain phenolic resin raw powder;

[0356] According to the mass ratio of the first precursor: phenolic resin raw powder: potassium hydroxide of 0.97:0.03:0.5, the three are mixed evenly, transferred to a box furnace under the protection of a nitrogen atmosphere, heated to 700°C, kept warm for 60 minutes, cooled to room temperature and transferred to a container, deionized water is added and stirred into a slurry, washed with deionized water until the pH is less than 10, and then excess hydrochloric acid is added, stirred, filtered, and washed until the pH is 6-7, and transferred to a 120°C oven and dried for more than 24 hours to obtain a hard carbon negative electrode material.

[0357] Comparative Example 5

[0358] The thermosetting phenolic resin was pre-carbonized at 500°C for 0.5h under nitrogen atmosphere, and air flow crushed to a carbonized material with a median particle size of about 9μm. The carbonized material: hydrochloric acid: deionized water were mixed in a mass ratio of 1:0.5:5, and after being immersed for 24h, it was washed with deionized water to pH=6-7, centrifuged and dried, and sintered at 1000°C for 1h in a box furnace under nitrogen atmosphere, and cooled to room temperature to obtain a first precursor.

[0359] According to the mass ratio of the first precursor to phenolic resin of 97:3, the phenolic resin was weighed, dissolved in an ethanol solvent, and stirred evenly to prepare a 5wt% phenolic resin ethanol solution, and then the first precursor was added under stirring, and a high-speed disperser was used to stir at a speed of 600r / min for 30min. The obtained mixed slurry was spray-dried, and the obtained powder was transferred to a box furnace, and cured at 150°C for 10h under nitrogen atmosphere protection, and cooled to room temperature to obtain a second precursor.

[0360] According to the mass ratio of the second precursor to potassium hydroxide of 1:0.5, the two are mixed evenly, transferred to a box furnace under the protection of a nitrogen atmosphere, heated to 700°C, kept warm for 60 minutes, cooled to room temperature and transferred to a container, deionized water is added and stirred into a slurry, washed with deionized water until the pH is less than 10, and then excess hydrochloric acid is added, stirred, filtered, and washed until the pH is 6-7, and transferred to a 120°C oven and dried for more than 24 hours to obtain a hard carbon negative electrode material.

[0361] Hitachi Hitachi S4800 scanning electron microscope was used to test the sodium and potassium contents by scanning electron microscope combined with X-ray energy spectrum at 1000 times. Panalytical X'Pert PRO MPD was used to test XRD, and the carbon layer spacing was measured according to the Scherrer formula. A Macbeth tester was used to perform nitrogen adsorption-desorption test at 77K, and the specific surface area was calculated by the BET formula. The results are shown in Table 1.

[0362] Table 1 Performance test data

[0363]

[0364] As shown in Table 1, in Examples 1-8, the specific surface area of ​​the obtained hard carbon negative electrode material is equivalent to that of the first precursor, while the carbon interlayer spacing (D002) is higher than the latter; the sodium or potassium content of the first precursor is 0, while the total sodium or potassium content of the obtained high-capacity hard carbon negative electrode material is 0.4-1.7wt%, and the specific surface area difference between the two is small. Among them, Example 7 uses a sodium- and potassium-containing composite active additive for high-temperature reduction reaction, and the sodium and potassium elements generated by reduction are co-intercalated to modify the second precursor. The obtained hard carbon negative electrode material has the highest carbon interlayer spacing (0.414nm), and contains sodium (0.2wt%) and potassium (0.3wt%). The mechanism is that a porous sacrificial carbon source is coated on the surface of the first precursor through coating and air oxidation. The active additive softened or melted at high temperature infiltrates into the pores of the coating layer and fully contacts with the sacrificial carbon source. Then, the sodium or potassium element generated by high-temperature reaction is evenly coated on the surface of the hard carbon and embedded between the carbon layers of the hard carbon negative electrode material through self-discharge reaction. Since the ion radius of sodium / potassium is larger than that of lithium ions, the carbon layer spacing of the hard carbon increases significantly after embedding sodium or potassium.

[0365] The specific button battery preparation method is as follows: hard carbon negative electrode material, conductive agent and binder are adjusted to a solid content of 50% with distilled water in a mass percentage of 91:3:6, and mixed evenly, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode sheet with a diameter of 8.4 mm and a surface density of 6±0.5 mg / cm 2 ; The lithium sheet is used as the counter electrode, 1 mol / L LiPF6 / EC+DMC+EMC (v / v=1:1:1) is used as the electrolyte, Celgrad2400 is used as the diaphragm, and the outer shell is a 2016 button battery shell.

[0366] The specific preparation method of the cylindrical battery is as follows: hard carbon negative electrode material, conductive agent and binder are dispersed in a solvent at a mass percentage of 94:1:5, mixed evenly, the solid content is controlled at 40%, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode sheet with a surface density of 6±0.5mg / cm 2 ; Then the NCM positive electrode prepared by traditional mature technology, 1 mol / L LiPF6 / EC+DMC+EMC (v / v=1:1:1) electrolyte, Celgard2400 separator and shell are assembled into 18650 cylindrical single battery using conventional production technology.

[0367] The test conditions for the specific capacity and initial efficiency of the materials obtained in Examples 1-8 and Comparative Examples 1-5 using the buckling method are as follows: tested on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd., first 0.1C discharge, cut-off voltage 1mV, then 0.1C charge, cut-off voltage 1.5V, the test results are shown in Table 2. The so-called platform capacity is the capacity value below 0.2V of the delithiation curve, and the so-called slope capacity is the capacity value above 0.2V of the delithiation curve, the results are shown in Table 2.

[0368] Table 2 Performance test data table

[0369]

[0370]

[0371] As shown in Table 2, the specific capacity of the high-capacity hard carbon negative electrode materials obtained in Examples 1-8 is higher than that of the first precursor. Further analysis shows that the slope area capacity of the high-capacity hard carbon negative electrode materials obtained in Examples 1-8 is higher than that of the first precursor, while the platform area capacity is equivalent to the latter. The slope area corresponds to lithium storage between the carbon layers of the hard carbon, and the platform area corresponds to lithium storage between the crystallites. This shows that the high-capacity hard carbon preparation method provided in the present application mainly increases the lithium storage sites between the carbon layers, and the lithium storage sites between the crystallites have not changed, revealing that sodium or potassium metal elements are embedded in the carbon layers of the hard carbon negative electrode material through self-discharge. Among them, Example 7 uses sodium and potassium co-intercalation to prepare a hard carbon negative electrode material containing both sodium and potassium, which has the highest capacity (489 mAh / g). This may be because when the second precursor is modified by a sodium-containing and potassium-containing composite active additive at the same time, the energy barrier of the reduction reaction is lower, and the generated sodium intercalation and potassium intercalation play a synergistic role, so that the carbon interlayer spacing of the obtained hard carbon reaches the maximum, and the increased lithium storage sites are the most. The first efficiency of the high-capacity hard carbon obtained in Example 1-8 is higher than that of the first precursor, because the reversible capacity of the former is higher than that of the latter, and the specific surface areas of the two are similar, and the irreversible capacity corresponding to the formation of the SEI film does not increase. As shown in Table 2, after phosphorus doping is used in Example 8, the specific capacity and ramp capacity are significantly improved compared with Examples 1-7.

[0372] 18650 battery test: tested on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd., with a voltage range of 2.0-4.2V. After capacity division, the energy density was tested, and then charged at 1C at room temperature, left to stand for 4 hours, and discharged at 1C. After another 4 hours of standing, the battery was charged at 10C. Based on the 1C and 10C charging capacities, the 10C / 1C charging capacity retention rate was calculated.

[0373] The test method for the electrode expansion rate is as follows: evenly select 10 points to test the electrode thickness, calculate the average value, assemble 18650 batteries with a voltage range of 2.0-4.2V, charge at 0.5C at room temperature, disassemble the battery in the glove box, evenly select 10 points to test the electrode thickness after expansion, calculate the average value, and divide the average electrode thickness after 0.5C charging by the average electrode thickness before charging, minus 1, to obtain the electrode expansion rate. The results are shown in Table 3.

[0374] Table 3 Test results

[0375]

[0376] As shown in Table 3, the 18650 battery energy density of the high-capacity hard carbon negative electrode material obtained in Examples 1-8 is as high as 168-215Wh / kg, which is higher than the corresponding first precursor and higher than Comparative Examples 1-5 (131-162Wh / kg), which shows that the method for preparing the hard carbon negative electrode material provided in the present application can significantly improve the energy density, which is because the method provided in the present application improves the capacity performance of hard carbon; the 10C / 1C capacity retention rate of the high-capacity hard carbon negative electrode material obtained in Examples 1-8 is as high as 74%-87%, which is higher than the corresponding first precursor and higher than Comparative Examples 1-5 (54%-65%). The pole piece expansion rate of the high-capacity hard carbon negative electrode material obtained in Examples 1-8 is as low as 0.9-1.9%, which is lower than the corresponding first precursor and lower than Comparative Examples 1-5 (2.5-5.0%). This is because after the alkali metal elements are embedded in the hard carbon interlayer, the hard carbon interlayer spacing becomes larger, and during the charging process, the impedance of lithium ions embedded in the carbon interlayer decreases, so the rate performance increases. In addition, the carbon interlayer spacing of the hard carbon is enlarged, and the material changes less after lithium insertion, so Examples 1-8 show lower lithium insertion pole piece expansion rate. Among them, the hard carbon obtained in Example 7 has the lowest pole piece expansion rate and the highest 18650 battery 10C / 1C charging capacity retention rate and energy density, indicating that the hard carbon negative electrode material prepared by sodium and potassium co-intercalation has the best performance.

[0377] In Comparative Example 1, a hard carbon source is directly mixed with an active additive, and then a hard carbon negative electrode material is prepared through curing, pre-sintering, sintering, purification, and pulverization processes. Compared with Example 1, the specific surface area of ​​the hard carbon negative electrode material of Comparative Example 1 is as high as 810 m 2 / g, the capacity and the first efficiency are both low. This shows that when the carbon source and the active additive react at high temperature, the mass proportion of the active additive is much smaller than that of the carbon source. Therefore, the main function of the active additive is to etch the carbon skeleton, resulting in an excessively high specific surface area of ​​the obtained hard carbon, an excessively high irreversible capacity of the generated SEI film, and a significant decrease in the first efficiency. The energy density of the 18650 battery is lower than that of Example 1.

[0378] The difference between Comparative Example 2 and Example 1 is that the first precursor is not sintered at high temperature, and the other conditions of the two are the same. Compared with Example 1, the specific surface area of ​​the hard carbon negative electrode material of Comparative Example 2 is still high, the carbon layer spacing (D002) is slightly improved, the capacity and first efficiency are lower than the hard carbon negative electrode material obtained in Example 1, and the energy density of the 18650 battery is much lower than that of Example 1. This shows that high temperature sintering of the first precursor is a necessary step in preparing high-capacity hard carbon negative electrode materials.

[0379] The difference between Comparative Example 3 and Example 1 is that no sacrificial carbon source is used to coat the first precursor, and the other conditions of the two are the same. Compared with Example 1, the carbon layer spacing (D002), specific capacity, and first efficiency of the hard carbon negative electrode material of Comparative Example 3 are lower than those of the hard carbon negative electrode material of Example 1, and are equivalent to the first precursor of Example 1, and the energy density of the 18650 battery is lower than that of Example 1. This shows that the carbon matrix of the second precursor has a dense structure after high-temperature sintering, and the active additive containing sodium or potassium cannot be reduced to sodium or potassium elemental. Therefore, coating the first precursor with a sacrificial carbon source is a necessary step in preparing a high-capacity hard carbon negative electrode material.

[0380] The difference between Comparative Example 4 and Example 1 is that phenolic resin raw powder is used instead of sacrificial carbon source coating, and the other conditions of the two are the same. The carbon layer spacing (D002), specific capacity, and first efficiency of the hard carbon negative electrode material of Comparative Example 4 are lower than those of the hard carbon negative electrode material of Example 1, and the energy density of the 18650 battery is lower than that of Examples 1-4. This shows that it is necessary to coat the surface of the first precursor with a sacrificial carbon source.

[0381] The difference between Comparative Example 5 and Example 1 is that air oxidation is not used, and the other conditions of the two are the same. The carbon layer spacing (D002), specific capacity, and initial efficiency of the high-capacity hard carbon negative electrode material obtained in Comparative Example 5 are lower than those in Example 1, and the energy density of the 18650 battery is lower than that in Example 1. This shows that after the surface of the first precursor is coated with a sacrificial carbon source, further oxidation is necessary.

[0382] Example 9

[0383] S1: Pre-carbonize the walnut shell at 500°C for 5h under a nitrogen atmosphere, and crush it by air flow to obtain a carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:8), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Mix the dried carbonized material and phosphorus pentoxide in a mass ratio of 90:10, sinter at 1000°C for 2h in a box furnace under a nitrogen atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0384] S2: Mix the two in a mass ratio of sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:1 to obtain an oxidizing solution. Add the third precursor to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:10, stir, heat to 50°C, keep warm for 10 hours, then cool and stand, pour off the supernatant after the slurry settles, dilute the remaining slurry 10 times with deionized water, centrifuge, wash with deionized water to pH = 6-7, and dry to obtain the fourth precursor;

[0385] S3: The fourth precursor, NaOH, and polystyrene are put into a VC heating machine at a mass ratio of 70:20:10, and the speed is set to 120 rpm / min. The temperature is raised to 650°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 1 hour, cooled, and the obtained material, concentrated hydrochloric acid, and deionized water are mixed at a mass ratio of 1:1:8, and allowed to stand for 24 hours. The mixture is washed with deionized water until the pH value is 6-7, centrifuged, and dried to obtain the fifth precursor;

[0386] S4: The fifth precursor was sintered at 1000° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0387] The SEM images of the obtained carbon materials are shown in Figure 5 shown.

[0388] Example 10

[0389] S1: Pre-carbonize sucrose at 600℃ for 5h under argon atmosphere, and air flow pulverize to obtain carbonized material with D50=5μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:0.5:5), let it stand for 24h, centrifuge, wash with deionized water until pH=6-7, and dry. Mix the dried carbonized material and diammonium hydrogen phosphate in a mass ratio of 91:9, sinter at 1050℃ in a box furnace under nitrogen atmosphere for 10h, and cool to below 100℃. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0390] S2: nitric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:0.5 by mass ratio, and the two are evenly mixed to obtain an oxidizing solution; the first precursor is added to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:5, stirred, heated to 45°C, kept warm for 2h, then cooled, allowed to stand, and after sedimentation, the supernatant is poured out, heated deionized water is diluted 8 times, centrifuged, washed with deionized water to pH = 6-7, and dried to obtain a fourth precursor;

[0391] S3: The fourth precursor, NaOH and glucose (D50 = 50 ± 5 μm) are put into a VC heating machine in a mass ratio of 80:17:3, the speed is set to 120 rpm / min, the temperature is increased to 820°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 0.5 h, and the material is discharged after cooling; the obtained material, concentrated hydrochloric acid and deionized water are mixed in a mass ratio of 1:1:8, and allowed to stand for 24 h, washed with deionized water to pH = 6-7, centrifuged, and dried to obtain the fifth precursor;

[0392] S4: The fifth precursor was sintered at 800° C. for 2 h in a box furnace under an argon atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0393] Embodiment 11

[0394] S1: Pre-carbonize the starch at 550°C for 10 hours in a helium atmosphere, and air flow crush to obtain a carbonized material with D50=8μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1.5:8), let it stand for 24 hours, centrifuge, wash with deionized water to PH=6-7, and dry. Mix the carbonized material and diammonium dihydrogen phosphate in a mass ratio of 89:11, sinter at 2500°C in a graphitization furnace under a nitrogen atmosphere for 3 hours, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0395] S2: Phosphoric acid (concentration 60wt%): CrO3 = 10:2 by mass ratio, the two are mixed evenly to prepare an oxidizing solution; the third precursor is added to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:8, stirred, heated to 80°C, kept warm for 4h, then cooled, allowed to stand, and after sedimentation, the supernatant is poured out, heated deionized water is diluted 5 times, centrifuged, washed with deionized water to pH = 6-7, and dried to obtain a fourth precursor;

[0396] S3: The second precursor, KOH and phenolic resin are put into a VC heating machine in a mass ratio of 70:25:5, the speed is set to 60rpm / min, the temperature is increased to 600℃ at 2℃ / min under a nitrogen atmosphere, and then kept warm for 2h, discharged after cooling, the obtained material, concentrated hydrochloric acid and deionized water are mixed in a mass ratio of 1:1:8, and allowed to stand for 24h, washed with deionized water until the pH is 6-7, centrifuged, and dried to obtain the fifth precursor;

[0397] S4: The fifth precursor was sintered at 600° C. for 5 h in a box furnace under a helium atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0398] Example 12

[0399] S1: Pre-carbonize the phenolic resin at 650°C for 4 hours under a nitrogen atmosphere, and air flow crush to obtain a carbonized material with D50=6μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:4), let it stand for 48 hours, centrifuge, wash with deionized water until the pH is 6-7, and dry. Mix the dried carbonized material and concentrated phosphoric acid in a mass ratio of 70:30, sinter at 1100°C in a graphitization furnace for 12 hours under a nitrogen atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0400] S2: Mix the two in a mass ratio of perchloric acid: KMnO4 = 10:1 to obtain an oxidizing solution; add the third precursor to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:9, stir, heat to 60°C, keep warm for 1h, then stop heating, let stand, pour out the supernatant after sedimentation, dilute 10 times with heated deionized water, centrifuge, wash with deionized water to pH = 6-7, dry to obtain carbon powder; put the carbon powder, KOH and NaOH in a mass ratio of 80:15:5 into a VC heating machine, set the speed to 80rpm / min, heat to 450°C at 2°C / min under a nitrogen atmosphere, then keep warm for 1h, cool and discharge to obtain a fourth precursor;

[0401] S3: The fourth precursor and iron powder (D50 = 50 ± 5 μm) are mixed in a mass ratio of 85:15, kept at 600 ° C in a box furnace for 0.5 h, cooled to below 100 ° C and discharged, the obtained material, concentrated hydrochloric acid and deionized water are mixed in a mass ratio of 1:1:8, left to stand for 24 h, washed with deionized water to pH = 6-7, centrifuged, and dried to obtain a fifth precursor;

[0402] S4: The fifth precursor was sintered at 700° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0403] Embodiment 13

[0404] S1: Pre-carbonize the asphalt at 450°C for 4h under a nitrogen atmosphere, and air flow crush to obtain a carbonized material with D50=8μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:0.8:10), let it stand for 36h, wash with deionized water until the pH is 6-7, centrifuge, and dry. Mix the dried carbonized material and phosphorus trioxide in a mass ratio of 95:5, sinter at 1000°C in a graphitization furnace for 2h under a nitrogen atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0405] S2: Sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:2 by mass ratio, and the two are evenly mixed to obtain an oxidizing solution; the third precursor is added to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:5, stirred, heated to 70°C, kept warm for 5h, then stopped heating, allowed to stand, and after sedimentation, the supernatant is poured out, heated deionized water is diluted 10 times, centrifuged, washed with deionized water to pH = 6-7, and dried to obtain a fourth precursor;

[0406] S3: The second precursor, Na2CO3, and Fe powder (D50 = 10 μm) were mixed in a mass ratio of 85:10:5, and put into a VC heating machine, and the speed was set to 120 rpm / min. The temperature was raised to 700°C at 1°C / min under a nitrogen atmosphere, and then kept warm for 1 hour. After cooling, the material was discharged, and the obtained material, concentrated hydrochloric acid, and deionized water were mixed in a mass ratio of 1:1:8, and allowed to stand for 24 hours. The mixture was washed with deionized water until the pH was 6-7, centrifuged, and dried to obtain the fifth precursor;

[0407] S4: The fifth precursor was sintered at 700° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0408] Embodiment 14

[0409] S1: Pre-carbonize the petroleum coke at 700°C for 0.5h under a nitrogen atmosphere, and crush it by air flow to obtain a carbonized material with D50=6μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:8), let it stand for 24h, wash with deionized water until the pH is 6-7, centrifuge, and dry. Mix the dried carbonized material and ammonium phosphate in a mass ratio of 85:15, sinter at 3000°C in a graphitization furnace under a nitrogen atmosphere for 6h, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0410] S2: Sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 8.5:1.5 are mixed evenly to obtain an oxidizing solution; the third precursor is added to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:10, stirred, heated to 50°C, kept warm for 5h, then stopped heating, allowed to stand, and after sedimentation, the supernatant is poured out, heated deionized water is diluted 10 times, centrifuged, washed with deionized water to pH = 6-7, and dried to obtain a fourth precursor;

[0411] S3: The fourth precursor, KOH and iron powder (D50 = 50 ± 5 μm) are put into a VC heating machine in a mass ratio of 68:17:15, the speed is set to 60 rpm / min, the temperature is increased to 450°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 0.8h, and the material is discharged after cooling. The obtained material, concentrated hydrochloric acid, and deionized water are mixed in a mass ratio of 1:1:8, and allowed to stand for 24h, washed with deionized water until the pH is 6-7, centrifuged, and dried to obtain the fifth precursor;

[0412] S4: The fifth precursor was sintered at 300° C. for 10 h in a box furnace under a helium atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0413] Embodiment 15

[0414] S1: Pre-carbonize the walnut shell at 500°C for 5h under an argon atmosphere, and crush it by air flow to obtain a carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:0.5:6), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Mix the dried carbonized material and sulfur powder in a mass ratio of 90:10, sinter at 1000°C for 2h in a box furnace under an argon atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve through 325 mesh, and obtain the third precursor;

[0415] S2: Mix the two in a mass ratio of sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:1 to obtain an oxidizing solution. Add the third precursor to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:10, stir, heat to 50°C, keep warm for 10 hours, then cool and stand, pour off the supernatant after the slurry settles, dilute the remaining slurry 10 times with deionized water, centrifuge, wash with deionized water to pH = 6-7, and dry to obtain the fourth precursor;

[0416] S3: The fourth precursor, NaOH, and polystyrene are put into a VC heating machine at a mass ratio of 70:20:10, and the speed is set to 120 rpm / min. The temperature is raised to 650°C at 2°C / min under an argon atmosphere, and then kept warm for 1 hour, cooled, and the obtained material, concentrated hydrochloric acid, and deionized water are mixed at a mass ratio of 1:1:8, and allowed to stand for 24 hours. The mixture is washed with deionized water until the pH value is 6-7, centrifuged, and dried to obtain the fifth precursor;

[0417] S4: The fifth precursor was sintered at 1000° C. for 2 h in a box furnace under an argon atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0418] Example 16

[0419] S1: Pre-carbonize the walnut shell at 500°C for 5h under a nitrogen atmosphere, and crush it by air flow to obtain a carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:0.5:6), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Mix the dried carbonized material, phosphorus pentoxide, and sulfur powder in a mass ratio of 90:6:4, sinter at 1000°C for 2h in a box furnace under an argon atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve through 325 mesh, and obtain the third precursor;

[0420] S2: Mix the two in a mass ratio of sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:1 to obtain an oxidizing solution. Add the third precursor to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:10, stir, heat to 50°C, keep warm for 10 hours, then cool and stand, pour off the supernatant after the slurry settles, dilute the remaining slurry 10 times with deionized water, centrifuge, wash with deionized water to pH = 6-7, and dry to obtain the fourth precursor;

[0421] S3: The fourth precursor, NaOH, and polystyrene are put into a VC heating machine at a mass ratio of 70:20:10, and the speed is set to 120 rpm / min. The temperature is raised to 650°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 1 hour, cooled, and the obtained material, concentrated hydrochloric acid, and deionized water are mixed at a mass ratio of 1:1:8, and allowed to stand for 24 hours. The mixture is washed with deionized water until the pH value is 6-7, centrifuged, and dried to obtain the fifth precursor;

[0422] S4: The fifth precursor was sintered at 1000° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0423] The process flow chart of Examples 9-16 is as follows Figure 6 The structural schematic diagram of the obtained carbon material is shown in Figure 7 As shown (perpendicular to the carbon plane, R is the doping group).

[0424] Comparative Example 6

[0425] S1: Pre-carbonize the walnut shell at 500℃ for 5h under nitrogen atmosphere, and air flow crush to obtain carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:8), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Mix the carbonized material and phosphorus pentoxide in a mass ratio of 90:10, sinter at 1000℃ for 2h in a box furnace under nitrogen atmosphere, and cool to below 100℃. Use a VC machine to evenly disperse the material, sieve with 325 mesh to obtain the third precursor;

[0426] S2: The third precursor, NaOH, and polystyrene are put into a VC heating machine in a mass ratio of 70:24:6, and the speed is set to 120 rpm / min. The temperature is increased to 650°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 1 hour, cooled, and the obtained material, concentrated hydrochloric acid, and deionized water are mixed in a mass ratio of 1:1:8, and allowed to stand for 24 hours. The mixture is washed with deionized water until the pH value is 6-7, centrifuged, and dried to obtain a fourth precursor;

[0427] S3: The fourth precursor was sintered at 1000° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0428] Comparative Example 7

[0429] S1: Pre-carbonize the walnut shell at 500℃ for 5h under nitrogen atmosphere, and air flow crush to obtain carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:8), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Sinter the dried carbonized material at 1000℃ in a box furnace under nitrogen atmosphere for 2h, and cool to below 100℃. Use a VC machine to evenly disperse the material, sieve with 325 mesh to obtain the third precursor;

[0430] S2: The third precursor, NaOH, and polystyrene are put into a VC heating machine in a mass ratio of 70:24:6, and the speed is set to 120 rpm / min. The temperature is increased to 650°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 1 hour, cooled, and the obtained material, concentrated hydrochloric acid, and deionized water are mixed in a mass ratio of 1:1:8, and allowed to stand for 24 hours. The mixture is washed with deionized water until the pH value is 6-7, centrifuged, and dried to obtain a fourth precursor;

[0431] S3: The fourth precursor was sintered at 1000° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0432] Comparative Example 8

[0433] S1: Pre-carbonize the walnut shell at 500°C for 5h under a nitrogen atmosphere, and crush it by air flow to obtain a carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:8), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Mix the dried carbonized material and phosphorus pentoxide in a mass ratio of 90:10, sinter at 1000°C for 2h in a box furnace under a nitrogen atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0434] S2: Mix the two in a mass ratio of sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:1 to obtain an oxidizing solution. Add the first precursor to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:10, stir, heat to 50°C, keep warm for 10 hours, then cool and stand, pour off the supernatant after the slurry settles, dilute the remaining slurry 10 times with deionized water, centrifuge, wash with deionized water to pH = 6-7, and dry to obtain the fourth precursor;

[0435] S3: The fourth precursor and NaOH are put into a VC heating machine at a mass ratio of 80:20, the speed is set to 120 rpm / min, the temperature is increased to 650°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 1 hour, cooled, the obtained material, concentrated hydrochloric acid, and deionized water are mixed at a mass ratio of 1:1:8, and allowed to stand for 24 hours, washed with deionized water until the pH is 6-7, centrifuged, and dried to obtain the fifth precursor;

[0436] S4: The fifth precursor was sintered at 1000° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0437] Comparative Example 9

[0438] S1: Pre-carbonize the walnut shell at 500°C for 5h under a nitrogen atmosphere, and crush it by air flow to obtain a carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:8), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Mix the dried carbonized material and phosphorus pentoxide in a mass ratio of 90:10, sinter at 1000°C for 2h in a box furnace under a nitrogen atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0439] S2: Mix the two in a mass ratio of sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:1 to obtain an oxidizing solution. Add the third precursor to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:10, stir, heat to 50°C, keep warm for 10 hours, then cool and stand, pour off the supernatant after the slurry settles, dilute the remaining slurry 10 times with deionized water, centrifuge, wash with deionized water to pH = 6-7, and dry to obtain the fourth precursor;

[0440] S3: The fourth precursor, NaOH, and polystyrene are put into a VC heating machine in a mass ratio of 70:20:6, and the speed is set to 120 rpm / min. The temperature is increased to 650°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 1 hour. After cooling, the obtained material, concentrated hydrochloric acid, and deionized water are mixed in a mass ratio of 1:1:8, and allowed to stand for 24 hours. The mixture is washed with deionized water to a pH of 6-7, centrifuged, and dried to obtain a carbon material.

[0441] Comparative Example 10

[0442] S1: Pre-carbonize the walnut shell at 500°C for 5h under a nitrogen atmosphere, and air flow crush to obtain a carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:8), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Mix the dried carbonized material and phosphorus pentoxide in a mass ratio of 90:10, sinter at 500°C for 2h in a box furnace under a nitrogen atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve through 325 mesh, and obtain the third precursor;

[0443] S2: Mix the two in a mass ratio of sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:1 to obtain an oxidizing solution. Add the third precursor to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:10, stir, heat to 50°C, keep warm for 10 hours, then cool and stand, pour off the supernatant after the slurry settles, dilute the remaining slurry 10 times with deionized water, centrifuge, wash with deionized water to pH = 6-7, and dry to obtain the fourth precursor;

[0444] S3: The fourth precursor, NaOH, and polystyrene are put into a VC heating machine at a mass ratio of 70:20:10, and the speed is set to 120 rpm / min. The temperature is raised to 650°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 1 hour, cooled, and the obtained material, concentrated hydrochloric acid, and deionized water are mixed at a mass ratio of 1:1:8, and allowed to stand for 24 hours. The mixture is washed with deionized water until the pH value is 6-7, centrifuged, and dried to obtain the fifth precursor;

[0445] S4: The fifth precursor was sintered at 1000° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0446] Comparative Example 11

[0447] S1: Pre-carbonize the walnut shell at 500°C for 5h under a nitrogen atmosphere, and crush it by air flow to obtain a carbonized material with D50=10μm. Mix the carbonized material, hydrochloric acid, and deionized water according to the mass ratio (carbonized material: concentrated hydrochloric acid: deionized water = 1:1:8), let it stand for 24h, centrifuge, wash with deionized water to pH=6-7, and dry. Mix the dried carbonized material and phosphorus pentoxide in a mass ratio of 90:10, sinter at 1000°C for 2h in a box furnace under a nitrogen atmosphere, and cool to below 100°C. Use a VC machine to evenly disperse the material, sieve with 325 mesh, and obtain the third precursor;

[0448] S2: Mix the two in a mass ratio of sulfuric acid (concentration 60wt%): H2O2 (concentration 30wt%) = 10:1 to obtain an oxidizing solution. Add the third precursor to the oxidizing solution in a mass ratio of the third precursor: oxidizing solution = 1:10, stir, heat to 50°C, keep warm for 10 hours, then cool and stand, pour off the supernatant after the slurry settles, dilute the remaining slurry 10 times with deionized water, centrifuge, wash with deionized water to pH = 6-7, and dry to obtain the fourth precursor;

[0449] S3: The fourth precursor and polystyrene are put into a VC heating machine at a mass ratio of 90:10, the speed is set to 120 rpm / min, the temperature is increased to 650°C at 2°C / min under a nitrogen atmosphere, and then kept warm for 1 hour, cooled, the obtained material, concentrated hydrochloric acid, and deionized water are mixed at a mass ratio of 1:1:8, and allowed to stand for 24 hours, washed with deionized water until the pH is 6-7, centrifuged, and dried to obtain the fifth precursor;

[0450] S4: The fifth precursor was sintered at 1000° C. for 2 h in a box furnace under a nitrogen atmosphere, cooled to below 100° C., and the material was evenly dispersed using a VC machine, and sieved with 325 mesh to obtain a carbon material.

[0451] Hitachi Hitachi S4800 scanning electron microscope was used to test the content of impurity elements and sodium / potassium elements by scanning electron microscope combined with X-ray energy spectrum at 1000 times. Nitrogen adsorption-desorption test was carried out at 77K using a Macbeth tester, and the specific surface area was calculated using the BET formula. The results are shown in Table 4.

[0452] Table 4 Specific surface area and element content test results

[0453]

[0454]

[0455] As shown in Table 4, in Examples 9-16, the specific surface area of ​​the obtained carbon negative electrode material is equivalent to that of the third precursor, while the carbon interlayer spacing (D002) is higher than the latter; the sodium and / potassium content of the third precursor is 0, while the sodium and / potassium content of the obtained carbon negative electrode material is 0.6-2.0wt%, and the specific surface area is equivalent to that of the former. This is because the carbon interlayer spacing of the obtained carbon negative electrode material is significantly increased by oxidizing and expanding the third precursor and then intercalating it with sodium and / potassium. At the same time, the third precursor is sintered to have a dense structure, which can overcome the etching of the material by oxidizing solutions, alkalis, etc., so the specific surface area does not increase significantly.

[0456] The specific button battery is prepared by a method known in the art: the carbon negative electrode material, the conductive agent and the binder are adjusted to a solid content of 50% with distilled water in a mass percentage of 91:3:6, and mixed evenly, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode sheet; a lithium sheet is used as a counter electrode, 1 mol / L LiPF6 / EC+DMC+EMC (v / v=1:1:1) is used as an electrolyte, Celgrad2400 is used as a diaphragm, and the shell uses a 2016 button battery shell.

[0457] The specific cylindrical battery is prepared by a method known in the art: the hard carbon negative electrode material, the conductive agent and the binder are dispersed in a solvent in a mass percentage of 94:1:5 and mixed evenly, the solid content is controlled at 40%, coated on a copper foil current collector, and vacuum dried to obtain a negative electrode plate; then the NCM positive electrode plate prepared by traditional mature technology, 1 mol / L LiPF6 / EC+DMC+EMC (v / v=1:1:1) electrolyte, Celgard2400 diaphragm, and shell are assembled into 18650 cylindrical single cells using conventional production processes.

[0458] The test conditions for the specific capacity and initial efficiency of the materials obtained in Examples 9-16 and Comparative Examples 6-11 using the buckling method are as follows: the test was conducted on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd., with a 0.1C discharge and a cut-off voltage of 1mV, followed by a 0.1C charge and a cut-off voltage of 1.5V. The test results are shown in Table 5. The so-called platform capacity is the capacity value below 0.2V of the delithiation curve, and the so-called slope capacity is the capacity value above 0.2V of the delithiation curve.

[0459] 18650 battery test: tested on the LAND battery test system of Wuhan Jinnuo Electronics Co., Ltd., with a voltage range of 2.0-4.2V. After capacity division, the energy density was tested, and then charged at 1C at room temperature, left to stand for 4 hours, and discharged at 1C. After another 4 hours of standing, the battery was charged at 10C. Based on the 1C and 10C charging capacities, the 10C / 1C charging capacity retention rate was calculated.

[0460] 6C / 6C cycle 1000-week capacity retention rate test method: Use 18650 batteries, charge and discharge at a constant current of 2.0-4.2V for 1000 cycles, and divide the capacity of the 1000th week by the capacity of the first week to get the 6C / 6C cycle 1000-week capacity retention rate.

[0461] The test method for the electrode expansion rate is as follows: evenly select 10 points to test the electrode thickness, calculate the average value, assemble 18650 batteries with a voltage range of 2.0-4.2V, charge at 0.5C at room temperature, disassemble the batteries in the glove box, evenly select 10 points to test the electrode thickness after expansion, calculate the average value, and divide the average electrode thickness after 0.5C charging by the average electrode thickness before charging, minus 1, to obtain the electrode expansion rate. The results are shown in Table 5.

[0462] Table 5 Performance test data

[0463]

[0464]

[0465] As shown in Table 5, in Examples 9-16, the specific capacity of the obtained carbon negative electrode material is higher than that of the third precursor, and the specific capacity, first efficiency, 10C / 1C rate charging capacity retention rate and 6C / 6C cycle capacity retention rate are higher than that of the third precursor, and the pole piece expansion rate is lower than that of the third precursor. Firstly, this is due to the preparation method of the carbon negative electrode material provided in the present application, which first improves the lithium storage capacity of the carbon negative electrode material by doping with impurities, and introduces a large number of sub-nanometer micropores into the structure, and then adopts sodium and / or potassium intercalation modification to increase the carbon layer spacing, and further increase the lithium storage sites between the carbon layers, so that the specific capacity and first efficiency of the obtained carbon negative electrode material are increased; secondly, as the carbon layer spacing increases, the internal resistance of lithium ion diffusion decreases, and the rate performance increases; finally, the carbon negative electrode material has a higher carbon layer spacing than the third precursor, and the volume change before and after charging (lithium insertion) is smaller than the latter, and the expansion performance is higher than the latter. Among them, Example 16 is co-doped with phosphorus, sulfur, and alkali metal elements (sodium), and has the best specific capacity, first efficiency, 10C / 1C rate charging capacity retention rate, and 6C / 6C cycle capacity retention rate.

[0466] Figure 8 The charging time-charging SOC-voltage curve of the carbon negative electrode material obtained in Example 9 under 5C (CC+CV) conditions. Figure 8It can be seen that the carbon negative electrode material obtained in Example 9 is charged under 5C (CC+CV) conditions for 10 min, and the capacity reaches 96.1% of the 1C (CC+CV) capacity, showing excellent fast charging performance.

[0467] The difference between Comparative Example 6 and Example 9 is that the third precursor has not been modified by oxidation expansion, while the third precursor of Example 9 has been modified by oxidation expansion, and the other conditions of the two are the same. Compared with Example 9, the sodium content and carbon layer spacing of the carbon negative electrode material obtained in Comparative Example 6 are equivalent to those of the third precursor and much smaller than those of Example 9. The specific capacity, first efficiency, and 10C / 1C charging capacity retention rate of Comparative Example 6 are lower than those of Example 9, while the expansion rate is higher than that of Example 9. This shows that oxidation expansion plays an important role in achieving sodium and / or potassium intercalation and improving the capacity, rate, and expansion performance of carbon negative electrode materials.

[0468] The difference between Comparative Example 7 and Example 9 is that the third precursor has not been doped with impurity elements, while Example 9 has been doped with impurity elements, and the other conditions of the two are the same. The sodium content and carbon layer spacing of the carbon negative electrode material obtained in Comparative Example 7 are higher than its third precursor and less than Example 9; the specific capacity, first efficiency, 10C / 1C charging capacity retention rate, and 6C / 6C cycle capacity retention rate of Comparative Example 7 are higher than its third precursor and lower than Example 9; the expansion rate of Comparative Example 7 is lower than its third precursor and higher than Example 9. This is because the third precursor of Comparative Example 7 is not doped with impurity elements, and there is a lack of sub-nanometer micropores in the carbon layer, which is not conducive to the diffusion of the oxidizing solution into the carbon layer. There is no doping group bonded to the carbon atom, and the sodium and / potassium intercalation lacks power, resulting in a relatively small amount of sodium / potassium intercalation into the carbon layer, and the capacity, rate, cycle, and expansion performance are less improved. This shows that the doping process before the oxidation expansion layer modification and reduction / intercalation reaction can effectively improve the material performance.

[0469] The difference between Comparative Example 8 and Example 9 is that no reducing agent is added to the fourth precursor before high temperature treatment, while a reducing agent is added to the fourth precursor of Example 9 before high temperature treatment, and the other conditions of the two are the same. The sodium content, carbon layer spacing, specific capacity, initial efficiency and rate performance, and pole piece expansion of the carbon negative electrode material obtained in Comparative Example 8 are similar to those of the third precursor, and are much smaller than those of Example 9. This shows that without the participation of a reducing agent, the alkali cannot be reduced to a single substance, and thus the alkali metal element intercalation modification cannot be completed. Therefore, it is necessary to add a reducing agent during the sodium / potassium reduction process of the fourth precursor.

[0470] The difference between Comparative Example 9 and Example 9 is that the fifth precursor is not subjected to high-temperature deoxygenation to obtain the carbon negative electrode material, while the fifth precursor of Example 9 is subjected to high-temperature deoxygenation to obtain the carbon negative electrode material, and the other conditions of the two are the same. The specific surface area, carbon layer spacing, sodium content, specific capacity, 10C / 1C charging rate performance, and pole piece expansion of the carbon negative electrode material obtained in Comparative Example 9 are equivalent to those in Example 9, while the first efficiency (71.1%) is much lower than that in Example 9 (86.1%). This is because the fifth precursor of Comparative Example 9 contains a large number of oxygen-containing groups, which will react with the electrolyte, resulting in a high irreversible capacity and a decrease in the first efficiency.

[0471] The difference between Comparative Example 10 and Example 9 is that the third precursor has not been sintered at high temperature, while the third precursor of Example 9 has been sintered at high temperature, and the other conditions of the two are the same. The specific surface area of ​​the carbon negative electrode material obtained in Comparative Example 10 is significantly higher than that in Example 9, and the sodium content is significantly lower than that in Example 9. The capacity is slightly higher than that in Example 9, the first efficiency is significantly lower than that in Example 9, and the 10C / 1C charging rate performance and pole piece expansion are the same as those in Example 9. This shows that the third precursor has not been sintered at high temperature, and has a loose structure. In the subsequent reaction process with the oxidizing solution and the alkaline additive, etching reaction mainly occurs, and the oxidation expansion effect is not significant. Therefore, it is necessary for the third precursor to be sintered at high temperature.

[0472] The difference between Comparative Example 11 and Example 9 is that the fourth precursor and the reducing agent react at high temperature, while the fourth precursor of Example 9 reacts with the alkaline additive and the reducing agent at high temperature, and the other conditions of the two are the same. The carbon interlayer spacing of the carbon negative electrode material obtained in Comparative Example 11 is equivalent to that of the third precursor. This is because the comparative example does not undergo alkali metal element intercalation modification. Therefore, after oxidation expansion, the carbon interlayer spacing first increases, and then after high temperature treatment, the carbon interlayer spacing returns to the level before oxidation expansion. The capacity performance, 10C / 1C charging rate performance and expansion performance of the carbon negative electrode material obtained in Comparative Example 11 are equivalent to those of its third precursor, all of which are lower than those of Example 9. Therefore, after the third precursor is doped with impurities and oxidized, it is necessary to further modify it by alkali metal element intercalation.

[0473] The electrode expansion rate and 6C / 6C cycle capacity retention rate of comparative examples 6, 8, and 11 are lower than those of embodiments 9-16, indicating that the synergistic effect of impurity doping and sodium / potassium intercalation improves the material structure stability, thereby improving the cycle performance of the carbon negative electrode material.

[0474] Embodiment 9-16 doped the doping group into the carbon skeleton, and then subjected to high temperature to obtain a first precursor with a dense structure and a large number of sub-nanometer micropores in the carbon layer, which is not easily etched by subsequent oxidizing solutions and alkaline additives to ensure that the target carbon negative electrode material has a high first efficiency; treated with an oxidizing solution, the oxidizing component diffuses to the edge of the carbon layer through the sub-nanometer micropores, inserts into the carbon layer and bonds with the carbon atoms to form oxygen-containing groups, thereby causing the carbon negative electrode material to undergo oxidation expansion to obtain a second precursor with increased carbon interlayer spacing; oxidation modification expands the carbon interlayer spacing and reduces the spatial steric hindrance of sodium / potassium intercalation; heteroelement doping, the doping group with lone pair electrons bonds with the carbon atom, through the induction effect, the adjacent carbon atoms have a higher electron cloud density and carry a partial negative charge, which is opposite to the charge of sodium / potassium ions, increasing the power of sodium / potassium intercalation, heteroelement doping and oxidation expansion synergistically reduce the energy barrier of sodium / potassium intercalation. Sodium / potassium elements generated by thermal reduction of the alkaline additive are intercalated, and the carbon interlayer spacing is further increased to obtain a third precursor with a large carbon interlayer spacing. On the one hand, high-temperature treatment removes oxygen-containing groups, reduces the occurrence of side reactions, and improves the conductivity and initial efficiency of the carbon negative electrode material. On the other hand, it improves the uniformity of sodium and / or potassium distribution, and the carbon interlayer spacing does not decrease significantly after high temperature, thereby obtaining a carbon negative electrode material co-doped with impurities and sodium / potassium and a large carbon interlayer spacing.

[0475] In addition, by co-doping with impurity elements and sodium / potassium elements, the conductivity of the carbon negative electrode is improved, the internal resistance is reduced, and the specific capacity, rate performance and cycle performance of the target carbon negative electrode material are further improved. The preparation method is simple to operate, low in cost, and suitable for large-scale production.

[0476] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0477] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a carbon negative electrode material, characterized in that: include: The carbon source is sequentially subjected to pre-treatment, intercalation reaction and post-treatment to obtain the carbon negative electrode material; the pre-treatment comprises: The raw materials including the carbon source are subjected to a first pre-carbonization and a first sintering to obtain a first precursor; the first sintering is performed under a first protective atmosphere; the temperature of the first sintering is 1000° C.-1300° C., and the time is 0.5 h-12 h; Mixing and coating materials including the first precursor and a sacrificial carbon source, and then curing and oxidizing to obtain a second precursor; The intercalation reaction comprises: The materials including the second precursor and the active additive for providing sodium or potassium are mixed, heated for reaction and then cooled to obtain the carbon negative electrode material; the heating reaction is carried out in a third protective atmosphere, the heating reaction temperature is 650°C-850°C, the heating rate is 0.5°C / min-5°C / min, and the insulation time is 20min-60min.

2. The method for preparing the negative electrode material according to claim 1, characterized in that: The carbon source includes a hard carbon carbon source, and the hard carbon carbon source includes at least one of phenolic resin, epoxy resin, melamine resin, furfural resin, acrylic resin, starch, glucose, sucrose, fructose, asphalt, almond shell, coconut shell, peach shell, walnut shell, jujube shell, polyfurfuryl alcohol, polyphenylene, polyaniline, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile.

3. The method for preparing the negative electrode material according to claim 1, characterized in that: The temperature of the first pre-carbonization is 400° C.-600° C., and the time is 0.5 h-4 h.

4. The method for preparing the negative electrode material according to claim 1, characterized in that: A first pulverizing process is further included after the first pre-carbonization and before the first sintering.

5. The method for preparing the negative electrode material according to claim 4, characterized in that: The median particle size of the pulverized material obtained by the first pulverization process is 2 μm to 40 μm.

6. The method for preparing the negative electrode material according to claim 4, characterized in that: The median particle size of the pulverized material obtained by the first pulverization process is 5 μm-20 μm.

7. The method for preparing the negative electrode material according to claim 4, characterized in that: The median particle size of the pulverized material obtained by the first pulverization process is 6 μm to 15 μm.

8. The method for preparing the negative electrode material according to claim 4, characterized in that: A first purification process is further included after the first pulverization process and before the first sintering process.

9. The method for preparing the negative electrode material according to claim 8, characterized in that: The first purification treatment includes: mixing materials including the crushed material, the first acid and water, soaking, first washing with water, and then first drying.

10. The method for preparing the negative electrode material according to claim 9, characterized in that: The first acid includes at least one of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, perchloric acid, acetic acid and benzoic acid.

11. The method for preparing the negative electrode material according to claim 9, characterized in that: The mass ratio of the pulverized material, the first acid and water is 1:(0.2-2):(5-10).

12. The method for preparing the negative electrode material according to claim 9, characterized in that: The immersion time is 12h-48h.

13. The method for preparing the negative electrode material according to claim 9, characterized in that: The material was washed with water to a pH of 6-7.

14. The method for preparing the negative electrode material according to claim 9, characterized in that: The water is pure water or deionized water.

15. The method for preparing the negative electrode material according to claim 9, characterized in that: The first drying process is performed at a temperature of 80°C to 120°C and for a time of 24h to 48h.

16. The method for preparing the negative electrode material according to claim 8, characterized in that: After the first purification and before the first sintering, the method further includes: performing a first doping on the purified material using a first impurity element source.

17. The method for preparing the negative electrode material according to claim 16, characterized in that: The first heteroelement source includes a phosphorus source and / or a sulfur source.

18. The method for preparing the negative electrode material according to claim 17, characterized in that: The phosphorus source includes at least one of phosphorus pentoxide, phosphorus trioxide, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphoric acid.

19. The method for preparing the negative electrode material according to claim 17, characterized in that: The sulfur source includes at least one of sulfur powder, sodium thiosulfate, ammonium sulfide, ammonium hydrogen sulfide and thioanisole.

20. The method for preparing the negative electrode material according to claim 16, characterized in that: The mass ratio of the purified material to the first impurity element source is (99-70): (1-30).

21. The method for preparing a negative electrode material according to claim 1, characterized in that: The first protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton.

22. The method for preparing the negative electrode material according to claim 1, characterized in that: The sacrificial carbon source includes at least one of asphalt, glucose, sucrose, fructose, epoxy resin, phenolic resin, furfural resin, urea-formaldehyde resin, acrylic resin, polystyrene, polyvinyl alcohol, polyvinyl chloride, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride and polyacrylonitrile.

23. The method for preparing the negative electrode material according to claim 1, characterized in that: The mass ratio of the sacrificial carbon source to the first precursor is (1-10): (99-90).

24. The method for preparing the negative electrode material according to claim 1, characterized in that: The mixed coating methods include solid phase mixed coating, liquid phase mixed coating and heating and melting coating.

25. The method for preparing the negative electrode material according to claim 1, characterized in that: The curing comprises: heating and curing the mixed and coated material under a second protective atmosphere.

26. The method for preparing the negative electrode material according to claim 25, characterized in that: The second protective atmosphere includes one or more of nitrogen, helium, neon, argon, and krypton.

27. The method for preparing the negative electrode material according to claim 25, characterized in that: The temperature of the heating curing is 100°C-300°C.

28. The method for preparing the negative electrode material according to claim 1, characterized in that: The oxidation comprises: subjecting the solidified material to a first heating treatment in an oxygen-containing atmosphere.

29. The method for preparing the negative electrode material according to claim 28, characterized in that: The mass percentage of oxygen in the oxygen-containing atmosphere is 5%-100%.

30. The method for preparing the negative electrode material according to claim 28, characterized in that: The oxygen-containing atmosphere is air.

31. The method for preparing the negative electrode material according to claim 28, characterized in that: The temperature of the first heating treatment is 200° C.-350° C., the heating rate is 0.5° C. / min-5° C. / min, and the holding time is 0.5h-3h.

32. The method for preparing a carbon negative electrode material according to claim 1, characterized in that: The active additive includes at least one of sodium hydroxide, sodium oxide, sodium carbonate, sodium bicarbonate, sodium nitrate, sodium hyponitrite, sodium hypochlorite, sodium oxalate, sodium acetate, sodium amide, sodium ethoxide, potassium hydroxide, potassium oxide, potassium carbonate, potassium bicarbonate, potassium nitrate, potassium hyponitrite, potassium hypochlorite, potassium oxalate, potassium acetate, potassium amide and potassium ethoxide.

33. The method for preparing the negative electrode material according to claim 1, characterized in that: The mass ratio of the second precursor to the active additive is 1:(0.5-2).

34. The method for preparing the negative electrode material according to claim 1, characterized in that: The particle size of the active additive is less than or equal to 30 meshes.

35. The method for preparing the negative electrode material according to claim 1, characterized in that: The second precursor and the active additive are mixed by a VC machine, the rotation speed of the VC machine is 500 r / min-3000 r / min, and the mixing time is 5 min-40 min.

36. The method for preparing the negative electrode material according to claim 1, characterized in that: The third protective atmosphere includes at least one of nitrogen, helium, neon, argon and krypton.

37. The method for preparing the negative electrode material according to claim 1, characterized in that: The cooling end point temperature is less than or equal to 120°C.

38. The method for preparing the negative electrode material according to claim 1, characterized in that: The post-processing includes: The cooled material is mixed with water, washed until the pH is less than or equal to 10, then a neutralizing substance is added, filtered and washed until the pH is 6-7, and then a second drying is performed.

39. The method for preparing the negative electrode material according to claim 38, characterized in that: The neutralizing substance includes at least one of hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, phosphoric acid, perchloric acid, acetic acid and benzoic acid.

40. The method for preparing the negative electrode material according to claim 38, characterized in that: The second drying process is performed at a temperature of 80° C. to 120° C. and for a time of 24 h to 36 h.

41. A method for preparing a carbon negative electrode material, characterized in that: include: The carbon source is sequentially subjected to pre-treatment, intercalation reaction and post-treatment to obtain the carbon negative electrode material; The pre-treatment includes: performing a second pre-carbonization on the raw materials including the carbon source to obtain a third precursor; Mixing materials including the third precursor and an oxidizing solution to perform oxidation expansion modification to obtain a fourth precursor; After the second pre-carbonization, the method further includes: performing a second doping on the second pre-carbonized material using a second impurity element source; The second doping comprises: mixing the second pre-carbonized material with a second impurity element source, and performing a second sintering in an inert gas atmosphere; the second sintering temperature is 850° C.-3000° C., and the time is 0.5 h-12 h; The second heteroelement source includes a phosphorus source and / or a sulfur source; The intercalation reaction comprises: The materials including the fourth precursor, the alkali additive and the reducing agent are mixed and then coated to obtain the fifth precursor; the alkali additive includes at least one of the hydroxide, oxide, carbonate, bicarbonate and nitrate of sodium or potassium; the coating treatment includes: heating and stirring under the fifth protective atmosphere, the heating and stirring temperature is 300°C-850°C, and the insulation time is 0.2h-1h.

42. The method for preparing the negative electrode material according to claim 41, characterized in that: The carbon source includes a difficult-to-graphitize carbon source and / or an easily-graphitizable carbon source.

43. The method for preparing the negative electrode material according to claim 42, characterized in that: The non-graphitizable carbon source includes at least one of a natural biomass carbon source, a plant extract carbon source and a polymer carbon source.

44. The method for preparing the negative electrode material according to claim 43, characterized in that: The natural biomass carbon source includes at least one of coconut shell, almond shell, pistachio shell, macadamia shell, date shell, peanut shell, walnut shell, peach shell, cotton, gelatin, sawdust, bamboo, straw, kelp and lignin.

45. The method for preparing the negative electrode material according to claim 43, characterized in that: The plant extract carbon source includes at least one of starch, glucose, sucrose, fructose and natural rubber.

46. ​​The method for preparing the negative electrode material according to claim 43, characterized in that: The polymer carbon source includes at least one of phenolic resin, epoxy resin, melamine resin, polyfurfuryl alcohol, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin and polyacrylonitrile.

47. The method for preparing the negative electrode material according to claim 42, characterized in that: The graphitizable carbon source includes at least one of asphalt, petroleum coke, mesocarbon microbeads and polyphenylene.

48. The method for preparing the negative electrode material according to claim 41, characterized in that: The temperature of the second pre-carbonization is 400° C.-700° C., and the time is 0.5 h-10 h.

49. The method for preparing the negative electrode material according to claim 41, characterized in that: The second pre-carbonization is performed under a fourth protective atmosphere, and the fourth protective atmosphere includes at least one of nitrogen, argon, neon, helium, xenon and krypton.

50. The method for preparing the negative electrode material according to claim 41, characterized in that: The phosphorus source includes at least one of phosphorus pentoxide, phosphorus trioxide, ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and phosphoric acid.

51. The method for preparing the negative electrode material according to claim 41, characterized in that: The sulfur source includes at least one of sulfur powder, sodium thiosulfate, ammonium sulfide, ammonium hydrogen sulfide and thioanisole.

52. The method for preparing the negative electrode material according to claim 41, characterized in that: The mass ratio of the second pre-carbonized material to the second impurity element source is (99-70): (1-30).

53. The method for preparing the negative electrode material according to claim 41, characterized in that: The inert gas atmosphere includes at least one of nitrogen, argon, neon, helium, xenon and krypton.

54. The method for preparing the negative electrode material according to claim 41, characterized in that: A second pulverizing process is further included after the second pre-carbonization and before the second doping.

55. The method for preparing the negative electrode material according to claim 54, characterized in that: The median particle size of the pulverized material obtained by the second pulverization process is 2 μm to 30 μm.

56. The method for preparing the negative electrode material according to claim 54, characterized in that: The median particle size of the pulverized material obtained by the second pulverization treatment is 4 μm to 20 μm.

57. The method for preparing the negative electrode material according to claim 54, characterized in that: The median particle size of the pulverized material obtained by the second pulverization treatment is 5 μm-10 μm.

58. The method for preparing the negative electrode material according to claim 54, characterized in that: A second purification process is further included after the second pulverization process and before the second doping process.

59. The method for preparing the negative electrode material according to claim 58, characterized in that: The second purification treatment comprises: mixing the materials including the pulverized material, the second acid and water, and then performing a first stirring, solid-liquid separation, washing the solid with water, and then performing a third drying.

60. The method for preparing the negative electrode material according to claim 59, characterized in that: The second acid includes at least one of hydrochloric acid, hydrofluoric acid, nitric acid, phosphoric acid and sulfuric acid.

61. The method for preparing the negative electrode material according to claim 59, characterized in that: The mass ratio of the crushed material, the second acid and the water is 1:(0.1-3):(5-10).

62. The method for preparing the negative electrode material according to claim 59, characterized in that: The first stirring time is 1 h to 24 h.

63. The method for preparing the negative electrode material according to claim 59, characterized in that: The solid was washed with water to an endpoint pH of 4-7.

64. The method for preparing the negative electrode material according to claim 59, characterized in that: The water is pure water or deionized water.

65. The method for preparing the negative electrode material according to claim 59, characterized in that: The temperature of the third drying is 100° C.-120° C., and the time is 24 h -48 h.

66. The method for preparing the negative electrode material according to claim 41, characterized in that: The oxidizing solution includes an oxidizing acid and an oxidizing aid.

67. The method for preparing the negative electrode material according to claim 66, characterized in that: The oxidizing acid includes at least one of concentrated sulfuric acid, concentrated nitric acid, concentrated phosphoric acid, perchloric acid and hypochlorous acid.

68. The method for preparing the negative electrode material according to claim 67, characterized in that: The mass fraction of the concentrated sulfuric acid is not less than 60wt%, and the mass fraction of the concentrated nitric acid is not less than 50%.

69. The method for preparing the negative electrode material according to claim 66, characterized in that: The oxidation aid includes at least one of H2O2, (NH4)2S2O8, CrO3 and KMnO4.

70. The method for preparing the negative electrode material according to claim 66, characterized in that: The mass ratio of the oxidizing acid to the oxidizing aid is 10:(0.1-2.0).

71. The method for preparing the negative electrode material according to claim 41, characterized in that: The temperature of the oxidation expansion layer modification is 30° C.-80° C., and the time is 1 h-48 h.

72. The method for preparing the negative electrode material according to claim 41, characterized in that: After the oxidation expansion layer modification, the materials in the slurry are allowed to settle, the supernatant is poured out, and the remaining slurry is diluted 5-10 times with water and centrifuged to obtain the fourth precursor.

73. The method for preparing the negative electrode material according to claim 72, characterized in that: The method further comprises a third purification step after the centrifugation: washing the solid matter obtained by the centrifugation with water.

74. The method for preparing the negative electrode material according to claim 73, characterized in that: The end point of the washing is when the pH of the washing system is 6-7.

75. The method for preparing the negative electrode material according to claim 73, characterized in that: The water is pure water or deionized water.

76. The method for preparing the negative electrode material according to claim 73, characterized in that: The washing is followed by a fourth drying.

77. The method for preparing the negative electrode material according to claim 76, characterized in that: The temperature of the fourth drying is 80° C.-120° C., and the time is 24 h -48 h.

78. The method for preparing the negative electrode material according to claim 41, characterized in that: The reducing agent includes high molecular polymer and / or iron powder.

79. The method for preparing the negative electrode material according to claim 78, characterized in that: The high molecular polymer includes at least one of starch, glucose, sucrose, fructose, natural rubber, phenolic resin, epoxy resin, melamine resin, polyfurfuryl alcohol, polyaniline, furfural resin, polyethylene glycol, polyethylene oxide, polyvinylidene fluoride, acrylic resin and polyacrylonitrile.

80. The method for preparing the negative electrode material according to claim 41, characterized in that: The heating and stirring are followed by cooling and discharging after heat preservation.

81. The method for preparing the negative electrode material according to claim 41, characterized in that: The mass ratio of the fourth precursor, the alkaline additive and the reducing agent is (70-90): (20-8): (10-3).

82. The method for preparing the negative electrode material according to claim 80, characterized in that: The heating and stirring speed is 30r / min-120r / min, and the heating rate is 1°C / min-5°C / min.

83. The method for preparing the negative electrode material according to claim 41, characterized in that: The coating treatment further includes a fourth purification: mixing materials including the material obtained by the coating treatment, the third acid, and water, and then performing a second stirring, standing, washing, and a fifth drying to obtain the fifth precursor.

84. The method for preparing the negative electrode material according to claim 83, characterized in that: The mass ratio of the material obtained by the coating treatment, the third acid and the water is 1:(0.1-3):(5-10).

85. The method for preparing the negative electrode material according to claim 83, characterized in that: The second stirring time is 1 h to 24 h.

86. The method for preparing the negative electrode material according to claim 83, characterized in that: The end point of the washing is when the pH of the washing system is 5-7.

87. The method for preparing the negative electrode material according to claim 83, characterized in that: The water is pure water or deionized water.

88. The method for preparing the negative electrode material according to claim 83, characterized in that: The fifth drying process is carried out at a temperature of 100° C. to 120° C. and for a time of 24 h to 48 h.

89. The method for preparing the negative electrode material according to claim 41, characterized in that: The fifth protective atmosphere includes one or more of nitrogen, helium, neon, argon and krypton.

90. The method for preparing the negative electrode material according to claim 41, characterized in that: The post-processing includes: subjecting the fifth precursor to a second heating treatment under a sixth protective atmosphere.

91. The method for preparing the negative electrode material according to claim 90, characterized in that: The temperature of the second heating treatment is 300° C.-1000° C., and the time is 0.5 h-5 h.

92. The method for preparing the negative electrode material according to claim 90, characterized in that: The sixth protective atmosphere includes at least one of a nitrogen atmosphere, an argon atmosphere, a neon atmosphere, a helium atmosphere, a xenon atmosphere, and a krypton atmosphere.

93. A carbon negative electrode material, characterized in that Prepared by the method for preparing the negative electrode material according to any one of claims 1 to 92; The carbon negative electrode material includes a carbon matrix and an alkali metal element. The alkali metal element is distributed between carbon layers of the carbon negative electrode material. The alkali metal element includes sodium and / or potassium. The carbon layer spacing of the carbon negative electrode material is 0.35nm-0.43nm.

94. The carbon negative electrode material according to claim 93, characterized in that The carbon matrix is ​​doped with heteroelements.

95. The carbon negative electrode material according to claim 94, characterized in that The heteroelement includes S and / or P.

96. The carbon negative electrode material according to claim 94, characterized in that The proportion of the impurity elements to the total mass of the carbon negative electrode material is no more than 4%.

97. The carbon negative electrode material according to claim 93, characterized in that The mass of the alkali metal element accounts for no more than 3% of the total mass of the carbon negative electrode material.

98. The carbon negative electrode material according to claim 93, characterized in that The alkali metal element exists between the carbon layers in the form of ACx, wherein A is Na and / or K.

99. The carbon negative electrode material according to claim 98, characterized in that x>8。 100. The carbon negative electrode material according to claim 93, characterized in that The specific surface area of ​​the carbon negative electrode material is 0.5 m 2 / g -10m 2 / g.

101. The carbon negative electrode material according to claim 93, characterized in that The true density of the carbon negative electrode material is 1.8 g / cc-2.6 g / cc.

102. The carbon negative electrode material according to claim 93, characterized in that The median particle size of the carbon negative electrode material is 2 μm-40 μm.

103. A lithium ion battery negative electrode, characterized in that Includes the carbon negative electrode material as described in any one of claims 93-102.

104. A lithium ion battery, characterized in that: Including the lithium ion battery negative electrode as described in claim 103.

105. An electrical device, characterized in that: Including the lithium ion battery as described in claim 104.

Citation Information

Patent Citations

  • Alkali Metal-Sulfur Secondary Battery Containing a Nano Sulfur-Loaded Cathode and Manufacturing Method

    US20180233784A1